The Oman Flora and Fauna Survey, 1975 - Harrison, David L. (Journal of Oman Studies, 1975)
The story of this expedition has its origin in the concern which has developed in recent years for the future of the Arabian Tahr (Hemitragus jayakari). This unique species of wild goat, confined to the mountain ranges of Oman, seemed to be threatened with extinction. During the spring of 1973 we formulated a plan for a National Park in the Jebel Akhdar Range. The area we selected is centred on the principal peak of Jebel Akhdar, and is almost rectangular, about 50 km across and 30 km from north to south, in the Hajar al-Gharbi, just south of Rostaq.
Keywords: Botanique -- Oman

Sohar Ancient Fields Project: Interim Project no. 1 - Wilkinson, T.J. (The Journal of Oman Studies, 1975)
During surveys conducted in 1973 as part of the Harvard Archaeological Survey of Oman, Williamson noted that the 9th-10th century trading city of Sohar had formerly been surrounded by a wide belt of intensive agriculture. This apparently stretched far inland of the present day limits of irrigated cultivation and its estimated area of some 6,100 hectares was calculated to be four times that of the present day cultivation within the same length of coast. Furthermore, this figure is only 700 hectares less than the entire area of irrigated land to be found today along the Batina from the Emirates border in the north to Al Khaburah in the south. To supply this area with irrigation water would have required a sophisticated system of water supply and the possible yield of such a system assumes added significance today when the water resources of the Batina are proving to be a limiting factor in agricultural development.

The Rock Art of Oman 1975 - Clarke, Christopher (The Journal of Oman Studies, 1975)
Keywords: Archéologie -- Oman

Survey and Excavations in Central Oman, 1974-75 - Cardi, Beatrice de (Journal of Oman Studies, 1975)
Keywords: Archéologie -- Oman

The Incense Port of Moscha (Khor Rori) in Dhofar - Pirenne, Jacqueline (Journal of Oman Studies, 1975)
Keywords: Archéologie -- Oman

A possible Link between the Jemdet Nasr and the Umm an-Nar Graves of Oman - Frifelt, Karen (Journal of Oman Studies, 1975)
Keywords: Archéologie -- Oman

Oman in the Third Millennium BCE - Hastings, Anne; Humphries, J. H.; Meadows, R.H. (Journal of Oman Studies, 1975)
In the course of two seasons of survey the Harvard Archaeological group has located seventeen settlements which, on the basis of associated ceramics, stone structures, lithic and copper remains, can best be attributed to the Third Millennium BCE. From the accumulated evidence, a preliminary idea of the conditions of life in Bronze Age Oman can be gleaned.
Keywords: Archéologie -- Oman

Notes sur ‘Abd-ar-Rahman Ibn Rustum - Zerouki, Brahim (Majallat Et-Tarikh, 1977)
Keywords: Dynastie rustumide

طبيعة الكتابات التاريخية حول الفترة العثمانية من تاريخ الجزائر - سعيدوني, ناصر الدين (المجلة التاريخية المصرية, 1978)

الاسلام و الحضاره العربيه فى شرق افريقيا - زكي, عبد الرحمن (المجلة التاريخية المصرية, 1974)

سياسة بريطانيا فى مسقط و زنجبار 1856 - 1873م - جاد, طه، (المجلة التاريخية المصرية, 1974)

الحیاة الاقتصادیة و الاجتماعیة فی سجلماسة عاصمة بنی مدرار - الجنحاني, الحبيب (المؤرخ العربي, 1978)

تیارات الفکر العربی المعاصر - الجنحاني, الحبيب (قضایا عربیة, 1979)
حبیب الجنحانیمجلة: قضایا عربیة; السنة السادسة، دیسمبر 1979 - العدد 8;

دور المرأة في الريف العماني - Letts, Sally E.; Birks, J.S. (مجلة دراسات الخليج والجزيرة العربية, 1977)
أن دور المرأة في المجتمع العماني الريفي ما زال محدودا للغاية ، ومع ذلك فأن هناك اتجاها تدريجيا نحو تخطي القيود إذ تأخذ المرأة على عاتقها الآن ، وبشكل متزايد ، بعض المسئوليات المنزلية الخاصة برب الأسرة الغائب عن المنزل . وهذا بالضرورة لا يعني توقف المرأة عن أداء مهامها التقليدية لكي تقوم بالمهام الجديدة ، بل يعني احتواء هذه المسئوليات الجديدة . غير أن هذا التوسع في دور المرأة لم يؤد إلى ارتفاع مكانتها ، وذلك لأن القبول العرفي بالمكانة الاجتماعية المتدنية للمرأة ما زال سائدا ، وهو يمثل عقبة رئيسة في وجه توسيع دور المرأة في حياة المجتمع ومساهمتها الفعلية في الحياة الاقتصادية للمناطق الريفية ومن غير المستطاع التغلب على هذه العقبة خلال جيل واحد . وما لم يقتنع المجتمع بأن باستطاعة النساء المشاركة في الحياة العامة بشكل كامل ، فلن يستطعن تقديم المساهمة التي بمقدورهن . ومن المهم دراسة أثر انخفاض عدد الرجال المتغيبين عن منازلهم على دور المرأة الموسع الجديد ، فهذا الاحتمال وارد جدا ومطلوب من نواح كثيرة نظرا للنقص الذي تعانيه القرى في الأيدي العاملة المحلية . فالنساء الريفيات في الوقت الحاضر يتولين لفترة مؤقتة فقط بعض المسئوليات الخاصة بالرجال التي تشغر خلال فترات عملهم بعيدا عن منازلهم . وهن الآن لسن في الطريق نحو إيجاد مكانة جديدة لأنفسهن ، بل يحاولن في غياب أزواجهن فقط احتلال مركز غير معترف به .. وبوجود مثل هذه الظروف لابد من التساؤل فيما إذا كانت عودة أرباب الأسر النهائية إلى منازلهم ستؤدي إلى تدني مرتبة النساء إلى المكانة التقليدية المغايرة لطموحاتهن بما ينطوي عليه ذلك من خلال ، أم هل سيكون بالمستطاع تنسيق جهود الرجال والنساء وتوحيدها على أساس جديد يمنح المرأة دورا جديدا ويدعمه . وإذا ما استطاع رجال الريف أن يقبلوا بدور المرأة الموسع الذي نتج عن هجرتهم بحثا عن العمل ، فسوف تجني عمان فوائد جمة من حيث تحسن إمكانات التنمية في الريف .

استعراض لبداية العلاقة الأمريكية التجارية والقنصلية مع سلطنة مسقط عمان( 1833 - 1856). - ستيفنس, ريتشارد (مجلة دراسات الخليج والجزيرة العربية, 1977)
كان للثورة الامريكية الاثر المباشر في العلاقات التجارية بغرب وشرق اسيا . حيث جزب السفن الامريكية وخاصة ساليم وماسو شوسيت اصل افريقيا الشرقية ومدغشقر وشبه الجزيزة العربية . وكان وكان الكابتن ادموند روبيرت هو اول من وصل إلى زنزبار في 1827 ولقد تم توقيع معاهدة رسمية بين سلطان ، سلطان مسقط – عمان عام 1832 . ولقد قام السلطان سعيد بال باحتياج شواطئ افريقيا الشرقية من الصومال إلى الموزمبيق ، كما قام بنقل العاصمة من مسقط إلى زنزبار 1832 وفي هذه الاجواء تم توقيع معاهدة صداقة وتبادل تجاري بين الولايات المتحدة والسلطان سعيد في 21 / سبتمبر 1833 ، والتي كانت ساريه حتى تاريخ 1958 ، ولم توفر تلك المعاهدة العلاقات الدبلوماسية وحسب بل ادت زيارة المعدي التجاري . بموجب التحكيم البريطاني في ، تم الفصل الكامل بين عمان – مسقط وزنزبار في حين خضعت زنزبار إلى السياسات الاستعمارية الالمانية والبريطانية . اما عمان – مسقط فقد تم اعلانها دولة مستقلة في 1934 وذلك عند وصول البعثه الدبلوماسية الامريكية إلى مسقط للاحتفال بمرور عام من توقيع المعاهدة التجارية .

ملاحظات وانطباعات حول ثورة المقران والشيخ الحداد - بن يوسف, سليمان بن داود (الأصالة, 1976)
Keywords: Dynastie rustumide

La situation ethno-linguistique à Zanzibar - Girenko, M. (Sovetskaja Etnografija Moskva, 1972)
Keywords: Linguistique -- Zanzibar

The Question of Nationalism and Education in Libya under Italian Rule - Appleton, Leonard (Libyan Studies, 1979)
Over thirty years of Italian rule in Libya (1911–1942), while leaving a considerable infrastructure of roads, schools and other public buildings, provided only a poor legacy in terms of skilled and educated Libyan manpower. This is attested by the fact that in 1951, there were only five graduates of Italian universities and perhaps ten from the Islamic University of Al-Azhar in Cairo. Moreover, there were no Arab directors of elementary schools or persons qualified for the non-Islamic professions or trained as agricultural experts. On the other hand, apologists of Italian rule emphasise that by 1942 Italy had made an important contribution towards solving some of Libya's most chronic problems. Although official statistics must be treated with caution, it is likely that by 1939 around 9676 pupils were enrolled in the halo-Arab schools, even if only 50% attended regularly. A further 147 students were said to be attending the School of Islamic Studies or al-Madrasah al-Islamiyya al-ùlyá at Tripoli which trained Islamic lawyers, school teachers and minor officials. 22 Moslem girls were also receiving training as nurses at the school of Princess Maria Pia originally set up in January 1936. The object of this paper, however, is not to narrate the achievements and defects of Italian rule in Libya, but to ask, what possible problems in the political, as opposed to the economic or other related fields, might have contributed to such a state of imbalance. Was it, for instance, some kind of “apartheid” policy on the part of the colonial regime that prevented Libyans from attending the excellent system of Italian secondary schools and so going on, like their Italian contemporaries, to become skilled artisans, technicians, engineers, doctors or administrators? Or was it because the mass of the Libyan population were so basically opposed to the Italian regime that they regarded attendance at the schools, whether elementary or secondary, as an act of collaboration with the hated oppressor? These are just two of the areas that would have to be explored by the historian before any explanation could be put forward of what can be termed the “central dilemma” of educational development in Libya under Italian rule.
Keywords: Enseignement -- Djebel Nefousa

Réflexions sur la Circoncision (Mzab, Metlili) - Fervel, Jacques (Le Saharien, 1972)
Keywords: Médecine -- Mzab

On Prehistoric Settlement and Chronology of the Oman Peninsula - Frifelt, Karen (East and West, 1975)
Keywords: Archéologie -- Oman

Libraries in Libya - Gallal, Ahmed M. (UNESCO bulletin for libraries, 1973)
Keywords: Bibliothèques -- Libye

The General Strike in Zanzibar, 1948 - Clayton, Anthony (The Journal of African History, 1976)
This article examines a three-week long strike in Zanzibar City in August and September 1948. The strike began among labourers from the mainland at work in Zanzibar port, but spread to all African work-people in the City after an unsuccessful attempt to break the strike by the government. This attempt had led to a major demonstration and confrontation at the entrance to the port, violence being only narrowly averted.While at one level the strike was a Zanzibar sequel to the strikes of the previous year in Mombasa and Dar es Salaam, in Zanzibar there was additional significance in the fact that the City and Island's work-force were in very large proportion men from the East African mainland. Zanzibar's dependence on mainland labour had begun in the early decades of the twentieth century. In those years mainland labour had been particularly well-paid, by the standards of the time. By the late 1940s however, mainland labour in Zanzibar was as poor as, perhaps poorer than, its mainland counterparts. Besides, the political structure of the Protectorate aggravated sentiments of alienation since mainlanders were not regarded as permanent residents for whom the government should have any particular concern: nor were mainlanders represented in the legislature.Even after the strike was over the colonial authorities saw only a need for labour reforms rather than political re-structuring to accommodate mainlanders. The strike however had briefly united all Africans, indigenous and mainlander. When, a decade later, this unity of Africans, mainlander and indigenous, town and plantation labourer and peasant, was re-formed, revolution followed. As a portent, therefore, Zanzibar's strike is of particular significance.
Keywords: Vie politique -- Zanzibar -- 1911-1960

La successione tardo triassica del Gebel di Garian (Libia) : esemplificazione del principio di Walther - Assereto, Riccardo (Rivista italiana di paleontologia e stratigrafia, 1970)
Keywords: Géologie -- Djebel Nefousa

الفتح المبين في سيرة البوسعيديين مقالة نقدية - الحميدان, عبداللطيف بن ناصر; عامر, عبد المنعم; عبد الله, محمد مرسي (مجلة كلية الآداب, 1979)
Keywords: Sources -- Oman

الفتح المبين في سيرة البوسعيديين - عامر, عبد المنعم; عبد الله, محمد مرسي; الحميدان, عبداللطيف بن ناصر (مجلة دراسات الخليج والجزيرة العربية, 1979)
Keywords: Sources -- Oman

التأصيل الفكري لجماعة التكفير والهجرة - الفحام, إبراهيم محمد (الأمن العام, 1977)

تاهرت : عاصمة الدولة الرستمية 161 هـ/ 777 - 778 م _ 296 هـ/ 909 م - الجنحاني, الحبيب (المجلة التونسية للعلوم الاجتماعية, 1975)
Keywords: Dynastie rustumide

دولة بنى يفرن الاباضية بتلمسان - بن يوسف, سليمان بن داود (الأصالة, 1975)

القوى المتصارعة فى المغرب خلال القرن الثانى الهجرى ودور ليبيا فيه - الغناي, مرجعة (مجلة كلية الآداب, 1973)

Hari̇ci̇li̇ği̇n Doğuşuna Tesi̇r Eden Bazi Sebepler - Fiğlali, Ethem Ruhi (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1972)

الفكر الاسلامي - ابو اليقظان, ابراهيم بن عيسى (الفكر الاسلامي, 1974)

هذه سبيل ادعوا الى الله على بصيرة - الحاج الناصر, محمد (الفكر الاسلامي, 1974)

تأثير المذاهب الاقتصادية في التيارات السياسية العالمية - الشيخ بالحاج, عمر (الفكر الاسلامي, 1974)

بشرى الجزائر وتحية وسلاما لفكر الاسلامي - بكلي, عبد الرحمن بن عمر (الفكر الاسلامي, 1974)

ومن يتبع غير الاسلام ديبا - بيوض, إبراهيم بن عمر (الفكر الاسلامي, 1974)

مالك بن نبي فلسفته ومؤلفاته - فخار, إبراهيم (الفكر الاسلامي, 1974)

Dossier Jerba - Mzabi, Hassouna; Jelassi, F.; Mimita, Mohamed Ajmi; Barbouch, Abdellatif (Art, Architecture, Aménagement, 1978)
Keywords: Architecture -- Djerba

L'économique et le social. Expériences tunisiennes - Cornet, Hubert (L'Afrique et l'Asie, 1970)
L'auteur, qui a dirigé pendant quatre ans un groupe de cent tisserands dans l'ile de Djerba, et qui s'est intéressé aussi à une association de maraîchers, réfléchit sur ses expériences. Il constate que les habitudes religieuses de base de l'Islam ont accoutumé les gens à se grouper en corporations, que celles-ci ne fonctionnent pas sur des schémas venus de la capitale, mais grâce à une confiance réciproque, résultant de contacts personnels, et à une claire conscience du bénéfice matériel qu'elles peuvent apporter. Il définit également avec pertinence l'attitude que doit avoir le conseiller technique européen, et le rôle qu'il peut jouer dans les pays en voie de développement (résumé de Maghre-Machrek, 1972/1, n° 49)
Keywords: Artisanat -- Djerba

Personnalités tunisiennes: Sadok Ben Jemaa (Mondes arabes, 1970)
Keywords: Biographies -- Djerba -- 20e siècle

Le sultanat d’Oman devant la rébellion du Dhofar: - Rondot, Philippe (Maghreb-Machrek, 1975)
Keywords: Dhofar

Die Djerbi in Tunesien. Soziologische Analyse einer nordafrikanischen Minderheit (Les Djerbiens en Tunisie. Analyse sociologique d'une minorité nordafricaine). Meisenheim am Glan, Anton Hain, 1970, 1 vol. 15 x 23 cm, 145 p., bibl. (Maghreb-Machrek, 1973)
L'auteur précise dans une sorte d'avant-propos que sa méthode, ses recherches, et l'analyse à laquelle il se livre pour faire apparaître les caractères de la minorité djerbienne, ne peuvent être enfermées dans un modèle, ni ne découlent d'une discipline · déterminée, car plusieurs d'entre elles, celles du sociologue, du politologue, de l'historien, du géographe, entre autres, se trouvent concernées. Et, de fait, il touche à chacune d'elle. Après avoir, dès les premières pages, évoqué la réforme commercial et le cas du Djerbien Salah ben Youssef, opposant au régime, assassiné à Francfort, il indique la répartition géographique des Djerbiens à l'aide de l'étude faite en 1941 par le contrôleur civil René Stablo. Puis il montre l'influence de l'histoire et du facteur religieux sur la formation de cette minorité et rappelle les faits concernant les Juifs, les Maltais ... Toute cette partie du livre, pour précise et intéressante qu'elle soit, se rapporte à des faits déjà exposés par divers auteurs. Plus originale est la partie consacrée à l'époque récente. L'auteur montre les répercussions qu'ont eues sur la minorité djerbienne le Youcefisme et la réforme commerciale, dont on ne peut exclure qu'elle fut dictée, au moins en partie, par une arrière-pensée politique, étant donné la place que tiennent les Djerbiens dans le commerce de détail. L'auteur a terminé son livre en 1968. Or, en 1969, à la suite de l'éviction de M. Ahmed Ben Salah, la réforme commerciale a été progressivement abandonnée. Les Djerbiens ont donc dû revenir en force. Un nouveau chapitre est à écrire.
Keywords: Recension

Mohamed Ali DABBOUZ : 1) Tarikh al-Maghrib ai-Kabir (Histoire du Grand Maghreb). Le Caire, 1963 et 1964, 3 vol., 471 p., 477 p. et 656 p., cartes et bibl. 2) Nahdat al-Djazair wa thawratuha (Essor de l'Algérie et Révolution), 3 vol. t. 1 (Damas, 1965), 404 p. ; t. Il et Ill (Alger, 1969 et 1971), 282 p. et 284., phot., bibl. - Mammeri, Hasseine (Maghreb-Machrek, 1973)
1. - C'est une tâche considérable qu'a entreprise M. Dabbouz, professeur de lettres et d'histoire à l'Institut d'al-Hayat (Guerara, Mzab). Il en justifie l'objet dans l'introduction du 2e volume (p. 7 et 8) en affirmant vouloir combler, au lendemain de l'indépendance de l'Algérie, une lacune, en apportant de nombreux faits inédits passés sous silence par "les impérialistes" et en écrivant en arabe l'histoire réelle dont nombre de faits ont été "falsifiés" à dessein par les historiens occidentaux. Le premier volume est consacré aux Berbères (cadre géographique, problème ethnique, civilisation), à Carthage, à la conquête romaine, à l'occupation vandale et aux Byzantins. Ce premier tome a le mérite de grouper en 471 pages une série de notions sans doute déjà connues mais que M. Dabbouz a reconsidérées à la lumière de ses propres lectures. Ses références sont aussi nombreuses que variées et il n'hésite pas à citer les passages importants d'historiens arabes sur lesquels il s'appuie. Condamnant tout ce qui a été écrit au sujet de l'origine des Berbères, il pense comme Ibn Khaldoun qu'ils sont les descendants de Mazigh b. Canaan b. Ham, qu'ils sont venus de Syrie et ne sont pas des Sémites. Dans le second volume l'auteur étudie avec soin l'établissement des Arabes, la résistance berbère conduite par la Kahina, la victoire finale de Hassan Ibn Nuoman et la conversion des autochtones à l'Islam. Puis l'historien cède la place au théologien et au juriste : soulèvement de Moawia contre Ali, exercice du pouvoir absolu, naissance du kharijisme, fin de la domination omeyyade, tout cela est groupé dans de nombreuses pages fort denses qui feront d'autant plus regretter l'absence d'un plan rigoureux. Le troisième tome est consacré exclusivement aux royaumes berbères où le kharijisme put s'épanouir en toute liberté. L'auteur s'étend longuèment et avec complaisance sur le règne des Imams rostémides désignés par la communauté des fidèles, et qui gouvernent selon le Coran et la Tradition prophétique. Le livre s'achève avec la fin de la dynastie rostémide et M. Dabbouz annonce la parution prochaine des ouvrages couvrant les règnes fatimide, almoravide, almohade, la domination turque puis française. 2. - Dans les trois volumes consacrés à "l'Essor de l'Algérie et à la Révolution", M. Dabbouz a su parfaitement analyser les principaux courants et, dans ses détails, l'évolution de l'histoire contemporaine du Maghreb ou plus exactement de l'Algérie. Son analyse des individualités majeures qui entreprirent de rétablir la foi dans sa pureté et d'arabiser l'Algérie "menacée par la francisation" est pertinente et il a su tirer tout le parti utile des travaux des orientalistes français, notamment de ceux de M. Charles-André Julien (comme il le signale dans le tome 1, p. 9 et 10). L'auteur s'attache d'autre part à montrer comment les Ulémas (les cheikh Ben Badis, al-Okbi, al-lbrahimi, puis plus tard le cheikh Bayyoud) ont su, "face au colonialisme français", préserver l'unité religieuse, la langue arabe et les traditions du peuple algérien. On regrettera peut-être tout le développement consacré dans le troisième tome au rôle joué par l'Institut d'al-Hayat du Mzab. Quoi qu'il en soit, cette "Histoire du Grand Maghreb" qui ne manque pourtant ni d'attrait, ni de vie, nous semble parfois discutable, trop souvent ponctuée de jugements personnels, et éloignée de cette sereine impartialité, généralement de mise chez les véritables historiens. Cette remarque de détail n'altère pas d'ailleurs la bonne impression d'ensemble que produit cette importante oeuvre (2 577 pages au total) d'une parfaite présentation et d'une typographie particulièrement soignée. Chaque volume se termine par des index scientifiquement établis, qui en facilitent le maniement. A ce seul titre, l'auteur mériterait notre reconnaissance.
Keywords: Recension

Le développement politique en Algérie. Etude des populations de la région du M'Zab. Paris, Armand Colin, coll. " Fondation nationale des sciences politiques, Etudes maghrébines 10 ". 1972, 1 vol. 15,5 x 24 cm, 175 p. (Maghreb-Machrek, 1973)
Mozabite lui-même, Baelhadj Merghoub était remarquablement bien placé pour analyser les comportements d'une société très fermée et particulariste. Nul observateur extérieur n'aurait réussi, comme il le fait , à décrire le jeu politique subtil auquel ont donné lieu les élections de 1967 et de 1969, à évaluer la force des courants réformistes et conservateurs, et le poids des facteurs religieux au sein d'une population scindée en deux groupes distincts : ibadites et malékites. Héritiers du système politique de Tahert, forts du contenu social et religieux du rite ibadite, les habitants du M'Zab surent résister à l'emprise de la colonisation française et conserver jusqu'à aujourd'hui leur originalité. Sont-ils, de ce fait, représentatifs de l'ensemble de l'Algérie, comme le suggère le titre ? On peut en douter. Cette étude n'en demeure pas moins une excellente monographie régionale.
Keywords: Recension

دراسة تاريخية حول مخطوط عقود الجمان في أيام آل سعود في عمان - أبو علية, عبدالفتاح (مجلة كلية العلوم الاجتماعية, 1978)

أهمية الأرشيف المصري في دراسة التاريخ الإجتماعي والإقتصادي والثقافي لبلاد المغرب - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1979)
Keywords: Emigration -- Djerba -- Egypte

دور المغاربة في تاريخ مصر في العصر الحديث. القسم الثاني: القرن التاسع عشر - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1978)
Keywords: Emigration -- Djerba -- Egypte

وثائق توضح دور الجالية المغاربة في تاريخ مصر في العصر العثماني القسم الثاني - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1977)
Keywords: Emigration -- Djerba -- Egypte

وثائق عن دور المغاربة في تاريخ مصر في العصر العثماني القسم الثالث - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1978)
Keywords: Emigration -- Djerba -- Egypte

وثائق عن دور الجالية المغاربة في تاريخ مصر في العصر العثماني القسم الثاني - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1977)
Keywords: Emigration -- Djerba -- Egypte

Enfants de Tunisie (Droit et Liberté, 1978)
Keywords: Recension

Extrait de textes sur Ouargla - M.B. (الأصالة, 1977)

Omani Silver - Hawley, Ruth (Proceedings of the Seminar for Arabian Studies, 1976)
Keywords: Archéologie -- Oman

Review of Oman and Southeastern Arabia: A Bibliographic Survey - Peterson, John E. (Middle East Journal, 1979)
Keywords: Recension

Review of Oman and Southeastern Arabia: A Bibliographic Survey - Smith, G. Rex (Bulletin (British Society for Middle Eastern Studies), 1979)
Keywords: Recension

Review of Oman: The Making of a Modern State - Peterson, John E. (Middle East Journal, 1978)
Keywords: Recension

Merghoub (Baelhadj) : Le Développement politique en Algérie. Étude des populations de la région du M'Zab - Valette, Jacques (Outre-Mers. Revue d'histoire, 1976)
Keywords: Recension

Review of Les parlers arabes de la région du Mzāb (Sahara algérien) - Singer, Hans-Rudolf (Die Welt des Islams, 1979)
Keywords: Recension

Review of Oman in the Twentieth Century; Yemen: The Politics of the Yemen Arab Republic - Feldman, Lily Gardner (The Annals of the American Academy of Political and Social Science, 1979)
Keywords: Recension

Review of Arabia without Sultans - Stork, Joe (Middle East Report, 1975)
Keywords: Recension

Review of The Laws of the Sultanate of Oman - Liebesny, Herbert J. (Middle East Journal, 1977)
Keywords: Recension

Oman Since 1856: Disruptive Modernization in a Traditional Arab Society - Rentz, George (Journal of the American Oriental Society, 1970)
Keywords: Recension

Review of Oman: The Making of a Modern State - Allen, Jr, Calvin H. (Middle East Studies Association Bulletin, 1978)
Keywords: Recension

Review of The, Sultanate, of Oman; Dofar: Guerrilla war on the Arabian Gulf - Albright, Charlotte F. (Middle East Studies Association Bulletin, 1979)
Keywords: Recension

Review of Oman and Its Renaissance.; Oman: The Making of a Modern State. - Porter, Brian (International Affairs, 1978)
Keywords: Recension

ملامح عن الحركة العلمية في ورجلان وضواحيها منذ انتهاء الدولة الرستمية حتى أواخر القرن 6 هـ - النامي, عمرو خليفة (الأصالة, 1977)
Keywords: Vie intellectuelle -- Ouargla

عمان فی کتابات جغرافی القرنین الثالث والرابع الهجری - دکسن, عبد الامیر عبد (اداب الرافدین, 1977)
لاشک أن تاریخ عمان فی العصور الوسطى لایزال بکرا ، لم یحظ بعد بما یستحقه من عنایة من لدن الباحثین المحدثین ففیما عدا النزر الیسیر مما کتب عن تاریخ هذا الجزء من الوطن العربی ، فانه لایزال بحاجة إلى المزید من الدراسات العلمیة الموضوعیة التی تکشف الغموض عنه وتجلى معالمه التی لایزال الکثیر منها - مع الاسف - خافیة علینا . ولعل هذا النقص فی الدراسات عن تاریخ عمان الوسیط یعود بالدرجة الأولى إلى قلة المادة التاریخیة وندرتها فی مصادرنا التاریخیة بشکل عام ، وذلک لان روایاتنا التاریخیة لم تکن لتعنی نفسها کثیرا فی العادة باحداث الأصقاع النائیة من الامبراطوریة العربیة الاسلامیة ، بل رکزت جل اهتمامها على أحداث مرکز الخلافة وکذلک على ما یجری فی تلک الاجزاء القریبة من المرکز ، وهکذا فان احداث تاریخ عمان لم یعالج الا باقتضاب شدید من جانب هذه المصادر . ومع ذلک فانه لمن الجائز أیضا أن تاریخ عمان فی هذه الفترة کان قد کتب شأنه شأن غیره من التواریخ الاخرى ولکنه لم یصل الینا بشکله التام المتکامل بسبب کون غالبیة سکان عمان فی هذه الفترة التی نحن بصددها من معتنقی مذهب الخوارج الاباضیة ، وهذا بلا شک یعنی أنهم کانوا خارجین على السلطة المرکزیة الشرعیة "الخلافة" .. وهکذا فمن غیر المستبعد أن تکون السلطة آنذاک قد لعبت دورا فی طمس أخبارهم ومنع تدوینها . هذا من جهة . ومن جهة أخرى فان الموقف العدائی بین السلطة وبینهم ربما کان قد جعل الرواة أنفسهم یتهیبون من تناقل مثل هذه الأخبار وتدوینها . على أنه مما یضیف إلى معلوماتنا عن تاریخ عمان فی هذه الفترة موضوعة البحث ، ویسد جزء من هذا النقص ، هو ما نجده فی کتب الجغرأفیین العرب والمسلمین وخاصة اولئک من القرنین الثالث والرابع الهجری التاسع والعاشر المیلادی ، لکون کتاباتهم تتسم بنوع من الاصالة بشکل عام ، رغم أن التأثر بجغرافیی الیونان یظهر فی البعض منها . ولسنا هنا فی مجال الکتابة عن تاریخ عمان عامة أو التطرق إلى حدث من احداثه ، بل نود أن نلفت النظر إلى المادة التی یقدمها هؤلاء الجغرافیون عن عمان وطبیعتها من خلال استعراضها مما قد یعین الباحث فی هذا المجال لیضیفها إلى ما هو متوفر فی کتب التاریخ العام و کتب التاریخ المحلی ، وبذلک تکتمل الصورة لدیه أو تکاد عن تاریخ هذا القطر الخلیجی فی العصر الوسیط .
Keywords: Géographie -- Oman

Notes et documents (André-Marie Louis 1912-1978) - Golvin, Lucien (Revue des mondes musulmans et de la Méditerranée, 1979)
Keywords: Biographies -- France

The Inscribed Sandals of Tippu Tip - Page, Melvin; Bennett, Patrick (Journal des africanistes, 1972)
Keywords: Tippo Tip (1837-1905); Zanzibar

Joint Irani-Omani Communiqué (Middle East Journal, 1974)
Keywords: Relations -- Oman -- Iran

Lewicki (T.) : Les Liaisons maghrébines, sahariennes et soudanaises de la ville de Ouargla au Moyen Age - Mauny, Raymond (Outre-Mers. Revue d'histoire, 1976)
Keywords: Recension

دراسات في النظم والعقائد الأباضية - خليفات, عوض محمد (مجلة مجمع اللغة العربية الأردني, 1979)
Keywords: Ibadisme -- thèmes et motifs

Les Fouilles de Tegdaoust - Robert, Denise S. (The Journal of African History, 1970)
Keywords: Archéologie -- Mauritanie

The Origins and Development of the Witu Sultanate - Ylvisaker, Marguerite (The International Journal of African Historical Studies, 1978)
Keywords: Zanzibar

Arabia without Sultans - McKnight, David (Australian Left Review, 1976)
This article was originally intended as a review of that excellent book by Fred Halliday, Arabia Without Sultans. However, I realise that there is not much point in commenting on a book about a situation of which many Australians are ignorant. Hence, my “ book review” has, as its main task, an account of some very important developments in the south of Arabia (defined as the peninsula including Saudi Arabia, North and South Yemen, Oman and the Trucial or Gulf States).
Keywords: Vie politique -- Oman -- 1970-2020

Jews under Muslim Rule in the late Nineteenth Century - Littman, David (The Wiener Library Bulletin, 1975)
Keywords: Judaïsme -- Djerba

أبو يعقوب يوسف الورجلانى وكتابه الدليل والبرهان: التراجم - الورجلانى, أبو يعقوب يوسف (الأصالة, 1977)

ورقلة من خلال النصوص الاجنبية - بلحميسى, مولاى (الأصالة, 1977)

Aperçu du mouvement scientifique à Ouaradjlane et dans ses environs, depuis l'extinction de la dynastie rostomide jusqu'a la fin du VIe siècle hégirien - Nāmī, ʿAmr Khalīfa al- (الأصالة, 1977)
Keywords: Vie intellectuelle -- Ouargla

لمحات من دور الدولة الرستمية فى ميادين الحضارة والفكر لبعض الباحثين القدامى والمتأخرين - البوعبدي, المهدي (الأصالة, 1977)
Keywords: Vie intellectuelle -- Rustumides

The nomadic Arabs and the origins of kharijites - Hanada, Nariaki (Bulletin of the Society for Near Eastern Studies in Japan, 1973)
As for the origins of Kharijites, many of Islamists have laid strss on their fanaticism and a narchy, and have attrbuted, in relaton to the effects of tue First Civil War, their origins, to the relization of the nomadic Arabs' inclination for the anarchy. Aocording to their opinions, the First Civil War was causeb by the clash of interests among vorious faction, but it's basic impulse was the reclamation of nomadic tribalism, and the outbreak of Kharijites movement should be considered as an expression of anarchistic tribalism. My opinion is that the origions of Kharijisnom was a form of Islamization of nomadic Arabs (“The First Civil Wat and the Kharijites”, World of Islam, VI, Tokyo, 1968, pp. 11-34). Many treatises on the Kharijites discussed the problem from the viewpoint of Itlamic Government. But in the present monograph I like to amplify my opinion in the former article on the tignificance of the First Civil War and the origins of Kharijites as examined from the nomadic Arabs' viewpoint, so as to find that the basic impulse of the First Civil War was not the tribalism, but the economic motives, and that the origins of Kharijism was based on the Islamization of nomadic Arabs.
Keywords: Kharijisme

A propos d'une expédition fatimide à Wargilan d'après Abu Zakariyya al-Wargilani - Nègre, André (Revue d'Histoire et de Civilisation du Maghreb, 1973)
Keywords: Prosopographie -- Afrique du Nord

دور الرستميين في وحدة مغرب الشعوب - فخار, إبراهيم (الأصالة, 1977)
Keywords: Dynastie rustumide

HLA Polymorphism in Israel : North African Jews from Libya - Bonné-Tamir, Batsheva; Bodmer, J. G.; Modai, J. (Tissue Antigens, 1978)
Keywords: Judaïsme -- Djebel Nefousa

Analysis of Genetic Data on Jewish Populations I. Historical Background, Demographic Features, and Genetic Markers - Bonne-Tamir, Batsheva; Karlin, Samuel; Kenett, Ron (American Journal of Human Genetics, 1979)
Part I describes the data sets on which the analysis of Part II is based. This covers the nature of the populations sampled, the extent to which the samples are representative, and a brief review of historical and demographic facts on the populations involved.
Keywords: Judaïsme -- Djerba

Misconceptions about the use of monsoons by dhows in East African waters - Datoo, B. A. (East African Geographical Review, 1970)
The East African coast has had maritime contacts with the peripheral lands of the Arabian Sea from time immemorial, and although dhows have been superseded by steamships since the latter part of the nineteenth century, a few still visit East Africa every year. Unless they are equipped with engines, movement of these sailing craft is dependent upon the monsoonal regime of the western Indian Ocean. However, popular ideas about monsoons constitute major misconceptions. These relate to the southern extent of the reliable northeast monsoon employed for the outward journey to East Africa, and the use of the southwest monsoon for the homeward passage to Arabia, Iran and India. This article seeks to correct these misconceptions on the basis of meteorological conditions in the western Indian Ocean, substantiated where possible by empirical evidence, contemporary and historical.
Keywords: Navigation -- Zanzibar

Some Notes on Diffusion of Qanat - Kobori, Iwao (Orient, 1973)

محمد وعبد الرحمان بن رستم في قرطبة - Molins, Maria Jesus Viguerra (الأصالة, 1975)
Keywords: Relations -- Tahert -- Andalousie

المجتمع التاهرتي في عهد الرستميين - عباس, إحسان (الأصالة, 1975)
Keywords: Dynastie rustumide

Colonialism and class formation in Zanzibar - Bhagat, Harkishan; Haroub, Othman (Utafiti, 1978)
Colonialism and class formation in Zanzibar. Explore a wide selection of African journal articles, citations and books bibliography for your research paper.
Keywords: Zanzibar

The Position of Qur'an Recitation in Early Islam - Juynboll, Gautier H. A. (Journal of Semitic Studies, 1974)

Slavery and Slave Revolts in the Sultanate of Zanzibar in the Nineteenth Century - Akinola, G.A. (Journal of the Historical Society of Nigeria, 1972)
Keywords: Esclavage -- Zanzibar

وثائق عن دور المغاربة في المجتمع الاسكندرية في العصر العثماني على ضوء وثائق السجل الاول من سجلات محكمة الاسكندرية الشرعية 27 محرم 1130-12 صفر 1131/1 جانفي 1718-5 جانفي 1719م - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1979)
Keywords: Emigration -- Djerba -- Egypte

التواسع الروماني نحو الجنوب الجزائري وآثاره الاقتصادية والاجتماعية - بشير, شنيقي محمد (الأصالة, 1977)

مصادر ثورة ابي يزيد مخلد ابن كيداد - عباس, إحسان (الأصالة, 1977)
Keywords: Ibn Kaydad

الحركة الاباضية في تاهرت وسدراتة وغرداية - بلغراد, محمد (الأصالة, 1977)

من قضاية التاريخ الرستمي - لقبال, موسى (الأصالة, 1977)
Keywords: Dynastie rustumide

مدينة ورقلة في رحلة العياشي - بلحميسي, مولاى (الأصالة, 1977)
Keywords: Récits de voyage -- Ouargla

الوضع في منطقة ورقلة قبل الاحتلال الفرنسي - زوزو, عبد الحميد (الأصالة, 1977)
Keywords: Ouargla -- Histoire

نماذج من مقاومة سكان الواحات - بوعزيز, يحيى (الأصالة, 1977)

ورقلة عروس مدائن الجنوب الجزائري - زبادية, عبد القادر (الأصالة, 1977)

أبو يعقوب يوسف الورجلاني وكتابه الدليل والبرهان - الجيلالي, عبد الرحمان (الأصالة, 1977)

أبو عمار الكافي والنسق الكلامي - الطالبي, عمار (الأصالة, 1977)

تطور ناحية ورقلة ما بين 1962-1975 - مكي, جلول (الأصالة, 1977)
Keywords: Ouargla -- Histoire

Early Christianity in Africa: North Africa, The Sahara, The Sudan, Central and East Africa - Brandl, Ludwig (Présence Africaine, 1975)

Le quercinois régicide Cavaignac, envoyé du Premier Consul à Mascate, en Arabie - Henri-Robert, Jacques (Bulletin de la Société des études littéraires, scientifiques & artistiques du Lot, 1977)
Keywords: Relations -- Oman -- France

Middle, Upper Jurassic and Lower Cretaceous sedimentary environments of the Djebel Nefusa region, northwestern Libya - Hodgkinson, Richard J.; Walley, Christopher D. (Annual report - Society for Libyan Studies, 1977)
Carbonate and clastic sediments of Jurassic and Cretaceous age are exposed along the fault-scarp of Djebel Nefusa in north-western Libya. Previous geological investigations have been mainly restricted to the eastern sector of the scarp. Recent studies by the authors in the western sector of Djebel Nefusa and on equivalent sediments in southern Tunisia have allowed the first regional interpretation of these rocks. The area studied lies geographically and geologically at the edge of the Saharan Platform, a large cratonic block, composed of rocks of Precambrian-Palaeozoic age. To the north and east lies a downfaulted sedimentary basin (Gabes-Sabratha Basin) containing a large thickness of Mesozoic sediments. The location of the sections measured along Djebel Nefusa are depicted in Fig.1. The stratigraphic nomenclature of the rock succession of Djebel Nefusa was first established in the east and continued laterally towards the west by later workers. Difficulties in the application of this nomenclature are presented by the recognition of facies changes previously overlooked by earlier investigators. However, as a framework for understanding these changes and the sedimentary processes which caused them, the stratigraphy erected by Magnier (1963) is adopted.
Keywords: Géologie -- Djebel Nefousa

Sources for the early history of Oman - Wilkinson, John Craven (المؤرخ العربي, 1978)

Les charters en Méditerranée - Spill, Jean-Michel (Annales de Géographie, 1976)
Keywords: Tourisme -- Djerba

Talbi ('Ammâr), Ara' al-khawârij al-kalâmîya; al-Mûjaz li-Abî 'Ammâr 'Abd alKâfî al-Ibâdhî [Les opinions des Khârijites concernant le c kalâm» (théologie dogmatique ?). Le Mûjaz de Abou 'Ammâr 'Abdelkâfî l'ibâdhite], Alger, SNED, 1978; 442 p. + 311 p. (bibliogr.). - Souriau, Christiane (Annuaire de l'Afrique du Nord, 1978)
Keywords: Recension

Routes de commerce et échanges en Afrique occidentale en relation avec la Méditerranée: un essai sur le commerce africain médiéval du XIe au XVIe siècle - Devisse, Jean (Revue d'histoire économique et sociale, 1972)
Keywords: Commerce transsaharien

Routes de commerce et échanges en Afrique occidentale en relation avec la Méditerranée: un essai sur le commerce africain médiéval du XIe au XVIe siècle - Devisse, Jean (Revue d'histoire économique et sociale, 1972)
Keywords: Commerce transsaharien

Britain and ‘The Oman War’: An Arabian entanglement - Peterson, John E. (Asian Affairs, 1976)
Keywords: Vie politique -- Oman -- 1970-2020

Dar es Salaam A sketch of a hundred years - Sutton, J.E.G. (Tanzania Notes and Records, 1970)
Keywords: Zanzibar

Décret n° 78-834 du 1er septembre 1978 portant approbation du plan d'aménagement du village de Midoun (commune de Jerba) - Nouira, Hédi (Journal officiel de la République tunisienne, 1978)
Keywords: Urbanisme -- Djerba

Review : Oman in the twentieth century. Croom Helm London, 1978, 286 p., appendices, bibliographie, index. - Rondot, Philippe (Politique étrangère, 1979)
Keywords: Recension

‏ورقلة ومنطقتها في العهد العثماني - سعيدوني, ناصر الدين (الأصالة, 1977)
Keywords: Relations -- Ouargla -- Empire ottoman

L’Ibaḍisme au XIIème siècle: la ʿAqida de Abu Sahl Yaḥyà (suite) - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1979)
Keywords: Foi -- Traité -- 12e siècle

Ali-Muâviye Mücâdelesi ve Harici Ayrilmasinin îbâdî kaynaklarin isiğinda incelenmesi - Veccia Vaglieri, Laura (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1973)
Keywords: Fitnah

Chapiteaux tardifs du limès de Maurétanie Césarienne dans la région de Tiaret - Cadenat, Pierre (Antiquités africaines, 1979)
Keywords: Archéologie -- Mzab

Recherches à Tihert-Tagdempt 1958-1959 - Cadenat, Pierre (Bulletin d'Archéologie Algérienne, 1978)
Keywords: Archéologie -- Mzab

Rouahia, site berbéro-romain inédit dans la commune de Kéria (Tiaret, Algérie) - Cadenat, Pierre (Antiquités africaines, 1978)
Keywords: Archéologie -- Mzab

La villa berbéro-romaine d'Aïn-Sarb (département de Tiaret, Algérie) suivi d'une Note sur l'ordre éolisant d'Aïn-Sarb - Cadenat, Pierre; Picard, Gilbert-Charles (Antiquités africaines, 1974)
Keywords: Archéologie -- Mzab

Bref aperçu sur les Archives Sahariennes du Dépôt des Archives d'Outre-Mer d'Aix en Provence - Boyer, Pierre (Revue de l'Occident musulman et de la Méditerranée, 1972)
Keywords: Archives -- Aix-en-Provence

Un établissement préromain dans la région de Tiaret (Oranie) - Cadenat, Pierre (Antiquités africaines, 1972)
Keywords: Archéologie -- Mzab

الفن الرستمي بتاهرت وسدراته - بورويبة, رشيد (الأصالة, 1977)
Keywords: Archéologie -- Sedrata

De nouveau sur la liste des tribus berbères d’Ibn Ḥawqal - Lewicki, Tadeusz (Folia Orientalia, 1971)

review : Rouvillois-Brigol: Le Pays de Ouargla (Sahara Algerien) - Smith, Richard L. (Middle East Journal, 1977)
Keywords: Recension

Review: John Townsend. Oman, the Making of the Modern State. New York: St. Martin's Press, 1977. Pp. 212. $16.95. - Landen, Robert Geran (Economic Development and Cultural Change, 1979)
Keywords: Recension

الرستميون قنطرة صلة بين الجزائر والاندلس من خلال الاباضية - Nogales, Salvador Gómez (الأصالة, 1977)
Keywords: Dynastie rustumide

Review : Water and tribal settlement in south-east Arabia: a study of the aflaj of Oman - Serjeant, Robert Bertram (Bulletin of the School of Oriental and African Studies, 1979)
Keywords: Recension

Review : KTZIA KATZ: The Hebrew language tradition of the community of Djerba (Tunisia). (Publications of the Hebrew University Language Tradi- tions Project, Vol. II.) vii, xxxv, 410 pp. Jerusalem: Hebrew Univer- sity Language Traditions Project, 1977. [In Hebrew.] - Ullendorff, Edward (Bulletin of the School of Oriental and African Studies, 1979)
Keywords: Recension

ابن الصغير مؤرخ الدولة الرستمية - القاضي, وداد (الأصالة, 1975)
Keywords: Dynastie rustumide

Arabic Materials in the Government Archives of Zanzibar - al-Naqar, ʿUmar (History in Africa, 1978)
This paper results from two visits to the Archives at Zanzibar in 1975 and 1976, lasting in all approximately three weeks. Access to these archives has not been an easy matter for some time, though more recently a few scholars have been able to secure permission to use them. This paper is an examination solely of the Arabic materials in the Archives, and may be of use to those who intend to use the Archives, particularly non-Arabic-speaking scholars. The collection was originally housed in the museum of Bayt al-Amānī before it was moved to its present site, a modern building centrally situated on the main road to the airport. There is a large reading room with an open shelf library containing various studies on Zanzibar, Zanzibar government publications, and a newspaper collection. Other documents are available on request from stacks housed in the lower part of the building. Regretably, however, no photocopying facilities are presently available. Copies of an inventory prepared in 1954 may be consulted in the reading room.
Keywords: Zanzibar

مجهودات الدولة الرستمية في نشر الحضارة اسلامية وتركيزها - بن يوسف, سليمان بن داود (الأصالة, 1977)
Keywords: Dynastie rustumide

Freund (Wolfgang) : Die Djerbi in Tunesien - Chaker, Salem (Revue de l'Occident musulman et de la Méditerranée, 1972)
Keywords: Recension

La poésie religieuse de l'ancien Islam - Gabrieli, Francesco (Revue des Études Islamiques, 1973)
Keywords: poésie kharijite

La Politica Africana Dell'italia Nelle Carte Di Pietro Bertolini - Gasbarri, Carlo (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 1975)
Keywords: Cartes -- Djebel Nefousa

Trucial Oman in the 16th and 17th Centuries - Cardi, Beatrice de (Antiquity, 1970)

Cholera in Matrah - Mackirdy, A. (Public Health Reports (1896-1970), 1970)
Keywords: Epidémies -- Oman

Some surprising aspects of Omani history - Hawley, Donald (Asian Affairs, 1976)

The Politics of Business: Relations between Zanzibar and Bagamoyo in the Late Nineteenth Century - Brown, Walter T. (African Historical Studies, 1971)
Keywords: Zanzibar

When did the donatist schism begin? - Frend, William; Clancy, K. (The Journal of Theological Studies, 1977)
Keywords: Donatisme

The Arabic Inscriptions on the Mosque of Abū Maʿrūf at Sharwas (Jebel Nefusa) - Lowick, Nicholas (Libyan Studies, 1973)
The medieval town of Sharwas – sometimes written Sharūs or Sarūs – figures in the writings of Ibn al-Warrāq (10th century A.D.), Ibn Hauqāl (10th century), al-Bakri (11th century), al-Idrīsi (12th century) and the anonymous author of the Kitāb al-Istibṣār (12th century). All are agreed that it was an important place, the chief settlement (umm qura) of the Jebel Nefusa. It had no congregational mosque (jāmic), but was one of the two towns in the Jebel provided with a minbār or pulpit. The name Abū Macrūf, as applied to the mosque and the surrounding ruins, does not appear in the medieval sources but certainly goes back many centuries in oral tradition. It refers to Abū Macrūf Wiyār ibn Jawād, a famous religious figure of the later 9th century who lived a short distance to the south-east of Sharwas and who was present at the battle of Mānū in A.H. 283/A.D. 896 - 7.A preliminary note on Sharwas and its mosque has already appeared in the Second Annual Report of this Society (pp. 10 - 11). There are no less than sixteen monumental inscriptions carved on separate blocks of stone outside and inside the Mosque. Most important for the dating of the structure is the two line inscription (no. 1, pl. VIa) in the tympanum of the west doorway. This is in the ornamented variety of Kufic usually referred to as ‘floriated’ The style is decidedly ‘provincial’ and does little credit to the engraver. Nevertheless it is possible to discern, in such features as the trifoliate ending to the dāl of waḥdahu in the first line, points of resemblance to the later of the two monumental inscriptions from Ajdābiyah published in the Society's Third Annual Report (p. 5, Pl. VIIIb). This is dated A.H. 351/A.D. 962. If it is true, as there suggested, that the floriated style was introduced into Libya between c. 922 and 962 A.D., then the inscription over the doorway at Sharwas is unlikely to be earlier than the second half of the the 10th century, allowing for the town's somewhat isolated position in the Tripolitanian hinterland. It may, indeed, be as late as the 12th century, if the present Mosque postdates the destruction of Sharwas, c. 1100.
Keywords: Architecture -- Djebel Nefousa; Archéologie -- Djebel Nefousa

al-Qasaba et d'autres villes de la route centrale du Sahara - Lange, Dierk; Berthoud, Silvio (Paideuma, 1977)
Trade of the Ibaḍīs of the Jabal Nafūsa with Kawar p. 34-36.
Keywords: Commerce transsaharien

Der Konflikt um Dhufar und die Aussichten auf seine Beilegung - Koszinowski, T. (Orient, 1976)
Keywords: Dhofar

France and Zanzibar, 1844 to the 1860s - Bennett, Norman Robert (The International Journal of African Historical Studies, 1974)
Keywords: Relations -- Zanzibar -- France

France and Zanzibar, 1844 to the 1860s - Bennett, Norman Robert (The International Journal of African Historical Studies, 1973)
Keywords: Relations -- Zanzibar -- France

Un village sur une presqu'île (Techniques et Architectures, 1975)
Keywords: Architecture -- Djerba

The Mysore grants, 1860: The appeal of Tippu Sultan's son - Knight, L.A. (South Asia: Journal of South Asian Studies, 1978)
Keywords: Tippo Tip (1837-1905)

Travail des femmes et production familiale en Tunisie - Ferchiou, Sophie (Questions Féministes, 1978)
Keywords: Artisanat -- Djerba

Guevara Through the Looking Glass: a View of the Dhofar War - Tremayne, Penelope (The RUSI Journal, 1974)
Keywords: Dhofar

La ḥāwiya: abrégé versifié des principes de nautique (ḥāwiyat al-’iḫtiṣār fī ’uṣūl ‘ilm al-biḥār) - Māğid, Aḥmad ibn (Bulletin d'Études Orientales, 1971)
Keywords: Navigation -- Oman

L'émigration tunisienne en particulier pour le Sud tunisien - Seklani, Mahmoud (Population, 1974)

La guérilla du Dhofar - Laliberté, Gérard (Études internationales, 1973)
Keywords: Dhofar

The Victoria Nyanza as a Trade Route in the Nineteenth Century - Hartwig, Gerald W. (The Journal of African History, 1970)
Keywords: Zanzibar

L'évolution des cités de l'Ifriquiya de la Conquête arabe au XVe Siècle - Ben Slimane, Ferid (Internationales Jahrbuch für Geschichts- und Geographie-Unterricht, 1977)

Djerba a Case Study in the Geography of Isolation - Karabenick, Edward (Journal of Geography, 1971)
Keywords: Géographie -- Djerba

Succession and Social Change in Tunisia - Ashford, Douglas E (International Journal of Middle East Studies, 1973)
Keywords: Commerce -- Djerba

Review: Socotra: An Archaeological Reconnaissance in 1967. D. BRIAN DOE. Henry Field and Edith M. Laird, eds. Foreword by Henry Field. Coconut Grove, FL: Field Research Projects, 1970. xxi + 156 pp., figures, maps, plates, notes, selected bibliography.n.p. (paper). - Muller, John (American Anthropologist, 1972)
Keywords: Recension; Zanzibar

The Myth of Trans-Saharan Trade during the Roman Era - Swanson, John T. (The International Journal of African Historical Studies, 1975)
Keywords: Commerce transsaharien

Guerrilla Warfare and Ideological Confrontation in the Arabian Peninsula: the rebellion in Dhufar - Peterson, John E. (World Affairs, 1977)
Keywords: Vie politique -- Oman -- 1970-2020

Review: Muscat and Oman: End of an Era, by Ian Skeet. London: Faber and Faber, 1974. 204 Pages. Maps. Illus. Gloss. Notes to P. 209. Appends. to P. 218. Index to P. 224. ?3.95. - Anthony, John Duke (Middle East Journal, 1975)
Keywords: Recension

Review : Oman. Musqat, Oman : Department of Information 1972. vii + 55 pages. Foreword. Illus. Appendices to p. 64. Bibl. No price indicated. - Anthony, John Duke (Middle East Journal, 1973)
Keywords: Recension

Towards a Description of the Traditional Pronunciation of the Jewish Community of Djerba - Katz, Ktzia (Proceedings of the World Congress of Jewish Studies / דברי הקונגרס העולמי למדעי היהדות, 1973)
Keywords: Judaïsme -- Djerba

Deux rapports de Salomon Reinach sur les Juifs de Tunisie au début du protectorat - Attal, Robert (Revue des études juives, 1979)
Keywords: Judaïsme -- Djerba

The Qur'an Reciter of the Battlefield and Concomitant Issues - Juynboll, Gautier H. A. (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1974)

The Qurra' in Early Islamic History - Juynboll, Gautier H. A. (Journal of the Economic and Social History of the Orient, 1973)
Keywords: Vie politique -- Irak

Die Völkerrechtlichen Verträge Des Sultanats Oman - Düster, Joachim (Verfassung und Recht in Übersee, 1971)

Some Notes on Religious Dissent in Nineteenth-Century East Africa - Amiji, Hatim M. (African Historical Studies, 1971)
Keywords: Zanzibar

al-Mujtamaʿ al-Tahārtī fī 'l-ʿAhd al-Rustamī - ʿAbbās, Iḥsān (Majallat al-ʿilm wa'l-īmān, 1972)
Keywords: Dynastie rustumide

Zanzibari Influence at the Southern End of Lake Victoria: The Lake Route - Holmes, C. F. (African Historical Studies, 1971)
Keywords: Zanzibar

Tripoli and Tripolitania: Conflict and Cohesion during the Period of the Barbary Corsairs (1551-1850) - McLachlan, Keith Stanley (Transactions of the Institute of British Geographers, 1978)

Khilāfat ʿUthmān wa-ʿAlī min Kitāb Kashf al-Bayān, Ta’līf Abī Saʿīd Muḥ. b. Saʿīd al-Azdī al-Qalhātī - Ibn ʿAbd al-Jalīl, Muḥammad (Ḥawliyyāt al-Jāmiʿa al-Tūnisiyya, 1974)
Chapters 17-22 from K. al-Kashf wa’l-Bayān. based on MS Or. 2606 in the British Museum.
Keywords: Fitnah

الشاعر هلال بن سعيد بن عرابة العماني - سلوم, داود (الخليج العربي, 1979)
See Mashriq, ʿUmānī, Hilāl b. Saʿīd: Dīwān Jawāhir al-Sulūk fī Madā’iḥ al-Mulūk wa-Tasliyat al-ʿĀshiq al-Mahlūk. Sallūm gives in his article a detailed study of this MS. On pp. 147-152 copies from the MS.
Keywords: Biographies -- Oman

al-Makhṭūṭāt al-ʿArabiyya fī Salṭanat ʿUmān - Wahībī, Muḥammad Saʿīd Nāṣir al- (مجلة معهد المخطوطات العربية, 1978)
Sixteen published works and 249 MSS (not all of them Ibāḍī works) out of the 2500 MSS then in MNHC are listed.
Keywords: Manuscrits -- Oman

Djāḥiz et les Khāridjites - Pellat, Charles (Folia Orientalia, 1970)
Keywords: Kharijisme

The medieval foundations of East African Islam - Pouwels, Randall L. (International Journal of African Historical Studies, 1978)
Keywords: Zanzibar

Review of: Oman since 1856: disruptive modernization in a traditional Arab society by Robert Geran Landen; Oman, a history by Wendell Philips; British interests in the Persian Gulf by Abdul Amir Amin]. - Kelly, J.B. (Middle Eastern Studies, 1970)
Keywords: Recension

Chekib Arslan et les mouvements nationalistes au Maghreb - Bessis, Juliette (Revue Historique, 1978)
Keywords: Réformisme

Les rapports anglo-senussi pendant la Grande Guerre (selon les sources françaises) - Kraïem, Mustapha (Revue d'histoire Maghrébine, 1977)

La question de l’annexion italienne de la Libye - Kraïem, Mustapha (Revue d'histoire Maghrébine, 1976)

مصلدر التاريخ المحلي لاقليم عمان - فوزي, فاروق عمر (مجلة المؤرخ العربي, 1979)
Short comments on sources for the history of Oman, i.e. Omani Siyar works, written by contemporary Omani politicians or scholars (such as Sīrat al-Bisyānī); the Nasab sources which deal with the history of Oman in a genealogical framework (such as al-ʿAwtabī’s Ansāb al-ʿArab); and the local chronicles which deal with the history of Oman in chronological order (such as al-Izkawī’s Kashf al-Ghumma). Of the first category the following works are mentioned: the Sīra of Shabīb b. ʿAṭiyya al-ʿUmānī; the Sīra of Abī ‘l-Mu’thir al-Ṣalt b. Khamīs al-Kharūṣī: K. al-Aḥdāth wa’l-Ṣifāt; the Sīra of Abū ‘l-Ḥasan ʿAlī b. Muḥ. al-Bisyānī: al-Ḥujja ʿalà man abṭala al-Su’āl fī ‘l-Ḥadath al-wāqiʿ bi-ʿUmān; the Sīra of Aḥm. b. ʿAbdl. al-Riqayshī al-Izkawī: Miṣbāḥ al-Ẓalām. Of the second category, the Nasab works: Abū ‘l-Mundhir Salma b. Muslim al-ʿAwtabī al-Ṣuḥārī: K. Ansāb al-ʿArab. And of the local chronicles: Sirḥān b. Saʿīd al-Izkawī: Kashf al-Ghumma al-jāmiʿ li-Akhbār al-Umma; Ibn al-Ruzayq: al-Fatḥ al-Mubīn fī Sīrat al-Sāda al-Būsaʿīdiyyīn; ʿAbdl. b. Ḥumayyid al-Sālimī: Tuḥfat al-Aʿyān bi-Sīrat Ahl ʿUmān.
Keywords: Sources -- Oman

ملامح من تاريخ حركة الخوارج الاباضية كما تكشفها مخطوطة الازكوي - فوزي, فاروق عمر (مجلة المؤرخ العربي, 1975)
On page 171: a description of the contents of the 40 paragraphs of the MS the author studied for his article (Kashf al-Ghumma). Pp. 179-186: the text of chapter 22 (Dhikr Intishār al-Madhhab al-Ibāḍī bi-Arḍ al-Maghrib wa-Dhikr A’immatihim wa-ʿUlamā’ihim).

Una rivista italo-araba d’inizio secolo: an-Nādī (Il Convito) - Scarabel, Angelo (Oriente Moderno, 1978)

Oman and ibadi Tribal Monarchic Syndrome - Saleem Khan, M.A. (Islam and the Modern Age, 1974)
Clements 1994, 152: a detailed study of Ibadhism during its medieval and modern history in Oman. Discusses the religious and political codes of Ibadhism and the history of its development in Oman and, in particular, the relationship between the elective Imamate and the interests of the Sultanate as a monarchic institution. Oman is particularly relevant to the study of Ibadhism as it is the only country with an Ibadhi majority; Ibadhism represents a much mellowed and moderate branch of the Kharijis of the first Muslim century. The Kharijis are examined to determine the development of contemporary Ibadhism, and this is followed by an account of its spread into Oman, the development of the Imamate and the struggle for political power between the Imamate and the Al Bu Said dynasty.
Keywords: Ibadisme -- Oman

Politics and religion in ʿUmān: a historical overview - Kaylani, Nabil M. (International Journal of Middle East Studies, 1979)
Keywords: Vie politique -- Oman

Les origines et l’islamisation de la ville de Tādmakka d’après les sources arabes - Lewicki, Tadeusz (Revue française d'histoire d'outre-mer, 1979)
the town of Tādmakka was an important Berber market lying on the southern edge of the Sahara in the area of the Adrar of Hoghas. The vast ruins of this town called El Souq are still visible. Tādmakka maintained relations at a great distance. According to al-Bakrī (1068), the caravan routes linked it with the towns of Qayrawān and Tripoli on the one hand and with the great political and trade centres of the western Sudan, Kawkaw (Goa) and Ghāna (Kumbi Saleh), on the other. Tādmakka was already flourishing in the 9th century. It was there that was born about 884, Abū Yazīd Makhlad b. Kaydād, the famous “man with an ass”, who was the son of a Berber merchant from Bilād al-Jarīd and belonging to a branch of the Zanāta. The Ibāḍī sources note also the presence of other Berber-Ibāḍī merchants from Zanāta, sometimes very rich. According to Ibn Ḥawqal (973-975) the inhabitants of the kingdom of Tādmakka called Banū Tānmak (Tādmak) belonged to a branch of the Ṣanhāja and were of black origin crossed with whites. On the contrary, the inhabitants of the capital of the kingdom, whom Yāqūt calls Zakrām (Akrām, for Aghram: castle) were of Zanāta origin. They were mostly Ibāḍī merchants from Djerid and other Ibāḍī districts of North Africa. As for the Ṣanhājan inhabitants of the Tādmakka kingdom, they long remained pagans and only became Moslem in the year 1109-1110, after the islamization of the town of Ghāna.
Keywords: Commerce transsaharien

Hâricîliğin doğuşu ve fırkalara ayrılışı - Fiğlali, Ethem Ruhi (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1978)
[The arising of Khārijism and its break-up into sects].
Keywords: Kharijisme

The significance of the slogan Lā Ḥukma illā li’llāh and the references to the Ḥudūd in the Traditions about the Fitna and the murder of ʿUthmān - Hawting, Gerald R. (Bulletin of the School of Oriental and African Studies, 1978)
Keywords: Fitnah

Ibâdiye’nin siyâsî ve itikâdî görüşleri - Fiğlali, Ethem Ruhi (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1976)
[The political and religious ideas of al-Ibāḍiyya].

Hadramaut, Oman, Dhufar: the experience of revolution - Kelly, J.B. (Middle Eastern Studies, 1976)
Keywords: Dhofar

Les noms propres berbères employés chez les Nafūsa médiévaux (VIIIe-XVIe siècle). (Observations d’un arabisant). Deuxième partie - Lewicki, Tadeusz (Folia Orientalia, 1974)
Keywords: Linguistique -- Djebel Nefousa

Les noms propres berbères employés chez les Nafūsa médiévaux (VIIIe-XVIe siècle). (Observations d’un arabisant). Première partie - Lewicki, Tadeusz (Folia Orientalia, 1973)

The Ibāḍites in Arabia and Africa - Lewicki, Tadeusz (Cahiers d'Histoire Mondiale, 1971)
The Ibāḍī community at Basra in the seventh to ninth centuries and the origins of the Ibāḍī states in Arabia and Africa. The Ibāḍīs in North Africa and the Sudan to the fourteenth century. On p. 81 a map of the Ibādī realm in North Africa in the Middle Ages. P. 99 note 77: the Ibāḍī collection of Smogorzewski in Lwów is now in Cracow. See Būʿaṣbāna 1991.

Un État soudanais médiéval inconnu: le royaume de Zāfūn(u) - Lewicki, Tadeusz (Cahiers d'études africaines, 1971)
The kingdom of Zāfūn was probably situated in the southern Sahel, between the Senegal river and the ruins of Koumbi Saleh. It became independent in 1076 A.D., after the Almoravids had conquered Ghana. Its flourishing started in the second quarter of the 12th century, when the king succeeded in dominating several nomadic Berbers in the western Sahara, who were part of the confederation of the Almoravids. In this period an important commercial route between western Sudan and the western Maghrib was realised. In 1150 the domination of the king of Zāfūn over the petty black states of the western Sudan ceased and the kings of Ghana overpowered Zāfūn again (Catalogue African Studies Centre in Leiden).

Les origines de l’Islam dans les tribus berbères du Sahara occidental: Mūsà ibn Nuṣayr et ʿUbayd Allāh ibn al-Ḥabḥāb - Lewicki, Tadeusz (Studia Islamica, 1970)

Moufdi Zakaria, nationaliste algérien et chantre du Maghreb arabe - Collot, Claude (Revue de l'Occident musulman et de la Méditerranée, 1978)
Keywords: Biographies -- Mzab -- 20e siècle

Hommage à Abū ‘l-Yaqẓān - Chikh, Slimane (Annuaire de l'Afrique du Nord, 1979)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973)

Ibadisme et société: la délibération des ʿAzzāba de Beni Isguen (27 Ram. 1399/20 août 1979) - Chikh, Slimane (Annuaire de l'Afrique du Nord, 1979)
The author places the text (182-186) in its religious, economic and social context. It concerns rules for more restrained marriage ceremonies. Mīzāb, situated between the oil and gas fields of Hassi R’mel and Hassi Mesaoud, has seen a spectacular economic flourishing. The influx of tourists, of workers from the North, modern communications and other modern developments have a serious impact on the relative isolation of the Mīzāb and on its traditional social structure.
Keywords: Droit coutumier -- Mzab; Moeurs et coutumes -- Mzab

Secret diplomacy and the Cyrenaican settlement of 1917 - Cole, Simon M. (Journal of Italian History, 1979)

The Municipal Council of Tunis, 1858–1870: A Study in Urban Institutional Change - Cleveland, William L. (International Journal of Middle East Studies, 1978)
Throughout the nineteenth century, the cities on the southern and eastern shores of the Mediterranean, Tunis, Alexandria, Beirut, Smyrna, and Istanbul among them, experienced an influx of foreign communities which, combined with an increase in the indigenous populations and new urban policies on the part of certain rulers, tended to disrupt customary patterns of urban relationships. Although the scholarship of recent years has provided a new awareness of the network of interrelationships which held together the segments of medieval Islamic urban society, studies on the nineteenth-century changes in those relationships as represented by the policies of Muhammad ῾Alī, Aḥmad Bey, and the Ottoman Tanzimat reformers, have tended to focus more on aspects of state and government than on cities as such. Yet cities, especially capital cities, reflect most intensely periods of social and institutional transition.
Keywords: Emigration -- Mzab -- Tunisie

Harvard archaeological survey in Oman, 1973: Sohar and the sea trade of Oman in the tenth century AD. - Williamson, Andrew (Proceedings of the Seminar for Arabian Studies, 1974)
Keywords: Archéologie -- Oman

Arab-Persian land relationships in late Sasānid Oman - Wilkinson, John Craven (Proceedings of the Seminar for Arabian Studies, 1973)
Papers from the 6th Seminar for Arabian Studies, held at the Institute of Archaeology, London, 27th-28th September 1972. Clements 1981, 64: this paper concentrates on late Sassanid rule in Oman during the 6th century A.D., when the Arabs evicted Sassanid ruling classes following the arrival of Islam and thus gained real control over the land. The writer examines the social structure during the period of Sassanid rule, and considers the hypothesis that the system of land utilization and irrigation was well established before the Arabs took over. “Maintaining their tribal organizations and bedu attitudes, there is no reason to suppose that the Arabs did anything to expand the prosperity of the land or create new establishments in pre-islamic times any more than they did when they became masters of the land".

Interview du Cheikh Ibrahīm Bayyuḍ sur l’organisation des Ibaḍites au Mzab - Cuperly, Pierre (Etudes Arabes, 1972)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

L’Ibaḍisme au XIIème siècle: la ʿAqida de Abu Sahl Yaḥyà - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1972)
Cuperly gives a biography of the author, a list of his works (with additions and corrections to Schacht 1956, 375-398), a general analysis of the Risāla and a description of each chapter, and a translation of extracts, with notes.
Keywords: Foi -- Traité -- 12e siècle

Muḥammad Aṭfayyash et sa Risāla shāfiya fī baʿḍ tawārīkh ahl Wādī Mizāb - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1972)
Cuperly gives a biography of the author, a list of his works (with additions and corrections to Schacht 1956, 375-398), a general analysis of the Risāla and a description of each chapter, and a translation of extracts, with notes.
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Prosopographie -- Afrique du Nord

Notes on Some Members of the Learned Classes of Zanzibar and East Africa in the Nineteenth Century - Martin, Bradford G. (African Historical Studies, 1971)
P. 525: this short paper is an attempt to draw a profile, to describe some of the features of the ʿUlamā’ class of Zanzibar and East Africa, based on the biographies of seven prominent members of this class who lived in the 19th century. These men show a wide range of interests, from poetry to juridprudence, from commerce to mysticism. Two of them might be described as “radicals”; the others were fairly conventional. In passing I have made a few comments on some significant points: the history of the “old Arabs” in East Africa, the role of the ʿUlamā’ class in the Muslim society of this time and place, the relations of the “learned” to trade and government, the interconnections of the two Muslim sects, Ibāḍīs and Shāfiʿīs, the literary and educational accomplishments of the ʿUlamā’, the participation of some of the ʿUlamā’ in the Qādirī and Shādhilī revivals of the 1880s and 1890s, the extent of Pan-Islamic influence in Zanzibar and East Africa. I would like to suggest a few priorities for further research in this field. The seven scholars who are treated are the Sunnī ʿUlamā’: Muḥyī ‘l-Dīn b. ʿAbdl. al-Qaḥṭānī al-Wā’ilī (c. 1790-1869), Manṣab b. ʿAlī (1863-1927), ʿAlī b. ʿAbdl. b. Nāfiʿ al-Mazrūʿī (1825-1894), ʿAbd al-ʿAzīz al-Amawī (1832-1896), ʿAbdl. b. Muḥ. Bā Kathīr al-Kindī (b. 1864), Aḥm. b. Sumayṭ (1861-1925), and the Ibāḍī scholar ʿAlī b. Khamīs b. Sālim al-Barwānī (1852-1886) (pp. 534-535), who became a Sunnī and was imprisoned for that by Sayyid Barghash. He had studied under the leading Ibāḍī Qāḍīs of Zanzibar in Barghash’s time and before, Yaḥyà b. Khalfān al-Kharūṣī and Muḥ. b. Sul. al-Mundhirī, and a visiting scholar from Oman, Khamīs b. Sālim al-Khaṣībī (Khuṣaybī). Martin cites frequently from Farsy 1944 and 1942. According to Kagabo 1991, 63, Barwānī was a Sunnī and was converted to Ibāḍism by the Ibāḍī sheikh Khamīs b. ʿAlī, and became a Sunnī again.
Keywords: Zanzibar

L’Adhān presso gl’Ibāḍiti - Rubinacci, Roberto (Folia Orientalia, 1970)
Mainly based on Jannāwunī: Kitāb al-Waḍʿ fī ‘l-Furūʿ. Pp. 285-290: translation of Jannāwunī, 222-237, chapter 3, on the Ādhān. Furthermore based on the commentary on the Kitāb al-Waḍʿ by Abū Sitta al-Qaṣbī (Abū ʿAbdl. Muḥ. b. ʿUmar b. Abī Sitta al-Qaṣbī al-Nafūsī), who used mainly the Kitāb al-Īḍāḥ of Abū Sākin ʿĀmir al-Shammākhī and Jayṭālī’s Qawāʿid and Qanāṭir.
Keywords: Jayṭālī, Ismāʿīl b. Mūsà (13..-1350); Orientalisme -- Italie

The Tripolitan war: a reconsideration of the causes - Folayan, Kola (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 1972)

The Ibāḍī imāma - Wilkinson, John Craven (Bulletin of the School of Oriental and African Studies, 1976)
Keywords: Imamat -- Ibadisme

The Siffin Arbitration Agreement - Hinds, Martin (Journal of Semitic Studies, 1972)
Keywords: Fitnah

Juifs maghrébins et commerce transsaharien du VIIIe au XVe siècle - Abitbol, Michel (Revue française d'histoire d'outre-mer, 1979)
Keywords: Judaïsme -- Mzab

Anne Kroell, Louis XIV, La Perse et Mascate, Société d'Histoire de l'Orient, Paris1977. 87 pp. ISBN 2 902558 02 3. Price: 30 FF. (Itinerario, 1979)
Keywords: Recension

The Jewish wedding in Tripolitania : A study in cultural sources - Goldberg, Harvey E. (The Maghreb Review, 1978)
Keywords: Judaïsme -- Djebel Nefousa

Notes on: 'Primitive Rebels' in the Pre-Colonial Maghreb - Seddon, David (The Maghreb Review, 1976)

Vernacular Architecture in the Maghreb - Some Historical and Geographical Factors - Petherbridge, Guy T. (The Maghreb Review, 1976)
Keywords: Architecture -- Sources

Die Djerbi in Tunesien. Soziologische Analyse einer nordafrikanischen Minderheit, Bd. 11 by Wolfgang Freund - Tetzlaff, Rainer (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte, 1974)
Keywords: Recension

Reviewed Work(s): Island of the Blest: Islam in a Libyan Oasis Community by John P. Mason - Holz, Robert K. (The International Journal of African Historical Studies, 1978)
Keywords: Recension

The Formation of the Omani Trading Empire under the Ya'aribah Dynasty (1624-1719) - El-Ashban, Abdul Aziz (Arab Studies Quarterly, 1979)
Keywords: Commerce -- Oman

التهديد العماني ونتائجه في اواخر القرن السابع عشر ومطلع القرن الثامن عشر - Lockhart, Laurence (الخليج العربي, 1978)

L'università Libica E Le Sue Pubblicazioni - Chiauzzi, Gioia (Oriente Moderno, 1975)

Dhofar: the achilles heel - Wakebridge, Charles (Middle East International, 1974)
Keywords: Dhofar

The Musandam Expedition 1971-72 Scientific Results: Part I: Discussion - Fraser, F. C.; Falcon, N. L.; Cornelius, P. F. S.; Hugh-Jones, P.; Bertram, G. C. L.; Shearman, D. J.; Glennie, K. W.; Shotton, F. W.; Vita-Finzi, Claudio; Roberts, D. G.; Robinson, G. P. G. (The Geographical Journal, 1973)
Keywords: Géographie -- Oman

Muscat in 1688: Engelbert Kaempfer’s report and engravings - Weisgerber, Gerd (Journal of Oman Studies, 1979)
Keywords: Récits de voyage -- Oman

A masterpiece of Omani 17th century architecture. The palace of Imam Bilarab bin Sultan al-Yaaraba at Jabrin - Galdieri, Eugenio (Journal of Oman Studies, 1975)
Keywords: Architecture -- Oman

The Ibrā’ and Muḍayrib area - Bonnenfant, Paul; Le Cour Grandmaison, Colette (Journal of Oman Studies, 1977)

Architecture and social history at Muḍayrib - Bonnenfant, Paul; Bonnenfant, Guillemette; Ḥārthī, Sālim b. Ḥamad b. Sul. al- (Journal of Oman Studies, 1977)
Keywords: Architecture -- Oman

The ʿAwāmr: specialist well- and falaj-diggers in Northern Interior Oman - Birks, J.S.; Letts, Sally E. (Journal of Oman Studies, 1976)
Keywords: Irrigation -- Oman

Spatial organization, tribal groupings and kinship in Ibrā’ - Le Cour Grandmaison, Colette (Journal of Oman Studies, 1977)

The archaeology of Oman: a preliminary discussion of the Islamic periods - Whitcome, Donald (Journal of Oman Studies, 1975)
Keywords: Archéologie -- Oman

The Julanda of Oman - Wilkinson, John Craven (Journal of Oman Studies, 1975)
Keywords: Vie politique -- Oman -- 749-751

Die Circumcellionen. Bemerkungen zum donatistischen Streit - Gottlieb, Gunther (Annuarium Historiae Conciliorum, 1978)
Keywords: Donatisme

Pour une Localisation du Royaume de Gaoga - Kalck, Pierre (The Journal of African History, 1972)

The Shawāwī population of Northern Oman: a pastoral society in transition - Birks, J.S. (Journal of Oman Studies, 1976)
Keywords: Nomadisme -- Oman

Bio-bibliographical background to the crisis period in the Ibāḍī Imāmate of Oman - Wilkinson, John Craven (Arabian Studies, 1976)
Keywords: Bibliographie -- Oman

Bayāsirah and Bayādīr - Wilkinson, John Craven (Arabian Studies, 1974)

Arabia in the fifteenth-century navigational texts - Tibbetts, G. R. (Arabian Studies, 1974)
Keywords: Navigation -- Oman

British financial advisers in Muscat during the interwar period - Peterson, John E. (Arabian Studies, 1979)
Keywords: Vie politique -- Oman -- 1970-2020

The revival of the Ibāḍī Imāmate in Oman and the threat to Muscat 1913-1920 - Peterson, John E. (Arabian Studies, 1976)
Keywords: Vie politique -- Oman -- 1970-2020

A St. George of Dhofar - Johnstone, Thomas Muir (Arabian Studies, 1978)
Keywords: Dhofar

Oath-taking and vows in Oman - Johnstone, Thomas Muir (Arabian Studies, 1975)
Keywords: Linguistique -- Oman

Folklore and folk literature in Oman and Socotra - Johnstone, Thomas Muir (Arabian Studies, 1974)
Keywords: Littérature -- Oman

Two South-Arabian tribes: al-Qarā and al-Ḥarāsīs - Dostal, W. (Arabian Studies, 1975)
Keywords: Tribalisme -- Oman

Graves of three descendants of Badr Bū Ṭuwayriq in Ẓafār of Oman - Carter, John (Arabian Studies, 1975)

Development or decline of pastoralists: the Banī Qitab of the Sultanate of Oman - Birks, J.S. (Arabian Studies, 1978)
Keywords: Nomadisme -- Oman

Bibliographical notes on European accounts of Muscat 1500-1900 - Bidwell, Robin (Arabian Studies, 1978)
Keywords: Récits de voyage -- Oman

Unpublished Wajīhid and Būyid coins from ʿUmān in the American Numismatic Society - Bates, Michael L. (Arabian Studies, 1974)
Keywords: Numismatique -- Oman

The first Saʿudi dynasty and ʿOman - Abdullah, M. Morsy (Proceedings of the Seminar for Arabian Studies, 1971)
Keywords: Vie politique -- Oman

Changes in the economy and political attitudes, and the development in culture on Coast of Oman between 1900 and 1940 - Abdullah, M. Morsy (Arabian Studies, 1975)
Keywords: Vie politique -- Oman

Chronology of the Kharijites Insurrection of Hamziyya in Sistan (8th-9th century). Its Outbreak and Fall - Składanek, Bogdan (Rocznik Orientalistyczny, 1979)
Keywords: Kharijisme

Ethnic Boundaries and Cultural Paradigms: The Case of Southern Tunisian Immigrants in Israel - Deshen, Shlomo (Ethos, 1976)
Keywords: Judaïsme -- Djerba

Geophysical Studies of North African Cenozoic Volcanic Areas: III. Garian, Libya - Ade-Hall, J. M.; Gerstein, Susann; Gerstein, Robert E.; Reynolds, Peter H.; Dagley, P.; Mussett, A. E.; Hubbard, T. P. (Canadian Journal of Earth Sciences, 1975)
Paleomagnetic and K/Ar whole rock absolute age data are described for material from the Garian area of Libya, centered at 13°E, 32°N. Within-unit cleaned paleomagnetic directions from the essentially unaltered lavas are very well defined and can almost certainly be taken as reliable measurements of the geomagnetic field direction during the initial cooling of each flow. However, the distributions of mean direction, from which the effect of repeated sampling of the field at one time has been removed, does not suggest that a reversing axial dipole field has been recorded in a representative manner. Both N and R groups of directions are azimuthally elongated, and the average poles for the N and R groups differ by 21°, or four times the 95% level uncertainty for each average pole. A number of possible physical explanations for the paleomagnetic results are discussed. The conventional overall average pole at 88°N, 123°E, δp: 3°, δm: 7 °does not differ significantly from the geographic pole, a result which agrees closely with that of Schult and Soffel (1973). However, the value of these overall average poles in estimating absolute plate motion must await an understanding of the sources of the asymmetries in the paleomagnetic data.
Keywords: Géologie -- Djebel Nefousa

West African Food in the Middle Ages according to Arabic Sources. By Tadeusz Lewicki with the assistance of Marion Johnson. London: Cambridge University Press, 1974. Pp. xvix + 262.£8. - Birmingham, David (The Journal of African History, 1977)
Keywords: Recension

The Omani Manuscript Collection at Muscat. Part II: The Early Ibāḍī Fiqh Work - Wilkinson, John Craven (Arabian Studies, 1978)
Keywords: Manuscrits -- Oman

The Omani Manuscript Collection at Muscat. Part I: A general Description of the MSS - Smith, G. Rex (Arabian Studies, 1978)
Keywords: Manuscrits -- Oman

Review of L'autobiographie de Hamed ben Mohammed el-Murjebi Tippo Tip (ca. 1840-1905), François Bontinck - Roberts, Andrew (Africa: Journal of the International African Institute, 1976)
Keywords: Recension; Tippo Tip (1837-1905)

Jacques GRAND'HENRY, "Les parlers arabes de la région du Mzab (Sahara algérien)" (Book Review) - Boudot-Lamotte, A. (Arabica, 1978)
Keywords: Linguistique -- Mzab; Recension

حركات الخوارج في المغرب وفي منطقة الخليج خلال العصر الاسلامي الاول - الجنحاني, الحبيب (الفكر, 1979)

الشعراء الخوارج والموت - شفيق, عزمي محمد (مجلة الآداب, 1977)
Keywords: Poésie kharijite

فى شعر الخوارج - الأسعد, عمر محمد (مجلة مجمع اللغة العربية بدمشق, 1977)
Keywords: Poésie kharijite

عوامل تدهور وانهيار الامامة الاباضية في عمان - فوزي, فاروق عمر (مجلة الآداب, 1977)
Keywords: Imamat -- Oman

كتاب طبقات المشائخ لأبي العباس أحمد بن سعيد الدرجيني " القرن السابع الهجري / الثالث عشر الميلادي " - الجنحاني, الحبيب (حوليات الجامعة التونسية, 1977)
Keywords: Prosopographie -- Afrique du Nord

الفرق في الإسلام : الخوارج - يعقوب, عبدالرحمن عبدالسلام (التوحيد, 1978)
Keywords: Kharijisme

الفرق في الإسلام (3) : الخوارج : طوائفهم وعقائدهم - يعقوب, عبدالرحمن عبدالسلام (التوحيد, 1978)
Keywords: Kharijisme

الفرق في الإسلام - 4 - : الخوارج : طوائفهم و عقائدهم - يعقوب, عبدالرحمن عبدالسلام (التوحيد, 1978)
Keywords: Kharijisme

دولة الخوارج في اليمن : بنو مهدي في زبيد 554 - 569هـ - صالح, محمد أمين (المجلة التاريخية المصرية, 1978)
Keywords: Kharijisme

آخر ما قاله أحد الخوارج لصغيره - البرادعي, خالد محي الدين (الموقف الأدبي, 1972)
Keywords: Kharijisme

حركات الخوارج في خراسان في القرنين الثاني والثالث للهجرة - الحديثي, قحطان عبدالستار علي (مجلة كلية الآداب, 1972)
Keywords: Kharijisme

الخوارج و قضية التحكيم - عبد الرازق, محمود إسماعيل (المجلة التاريخية المصرية, 1973)
Keywords: Kharijisme

تصريح علني بعد اغتيال أحد الخوارج - الشرقاوى, علي (الموقف الأدبي, 1973)
Keywords: Kharijisme

ملامح من تاريخ حركة الخوارج الاباضية كما تكشفها مخطوطة الازكوي - فوزي, فاروق عمر (مجلة المؤرخ العربي, 1974)
Keywords: Kharijisme

خلافة عثمان وعلي من كتاب "الكشف والبيان" - ابن عبد الجليل, محمد (حوليات الجامعة التونسية, 1974)
Keywords: Fitnah

العلاقات التجارية بين المغرب والسودان عبر الصحراء من القرن 6 الى القرن 8ه ودور تلمسان فى هذا الميدان - عطا الله, دهينة (الأصالة, 1975)
Keywords: Commerce transsaharien

في الشعر السياسي - حسان, تمام (المناهل, 1975)
Keywords: Recension

اعادة النظر فى ادب الخوارج - الكتاني, جعفر (البحث العلمي, 1972)
Keywords: Kharijisme

نظرة تقييمية لدراسات تاريخية حديثة عن حركات الخوارج فى المغرب العربى فى العصر الاوسط - الجنحاني, الحبيب (الأصالة, 1973)
Keywords: Kharijisme

الخوارج - توفيق, أرشد (مجلة الآداب, 1970)
Keywords: Kharijisme

الحياة الدينية في جربة - ابن مرزوق, الصادق (مجلة الهداية, 1976)
Keywords: Vie religieuse -- Djerba

Quelques notes... sur une île de Tunisie : Djerba la Douce - Gaury, René (Société des lettres, sciences et arts du Saumurois, 1979)
Keywords: Récits de voyage -- Djerba

Pourquoi l’Association de Sauvegarde de Djerba ? - Bouabid, Moncef (Echanges, 1979)
Keywords: Architecture -- Djerba

West African Food in the Middle Ages, According to the Arabic Sources - Miracle, Marvin (The American Historical Review, 1976)
Keywords: Recension

West African Food in the Middle Ages - Norris, Harry Thirlwall (Bulletin of the School of Oriental and African Studies, 1975)
Keywords: Recension

West African Food in the Middle Ages: According to Arabic Sources - de Gregori, Thomas R. (Technology and Culture, 1975)
Keywords: Recension

Arabic External Sources for the History of Africa to the South of Sahara - Martin, Bradford G. (The International Journal of African Historical Studies, 1973)
Keywords: Recension

West African Food in the Middle Ages - Hogendorn, Jan (The International Journal of African Historical Studies, 1975)
Keywords: Recension

West African Food in the Middle Ages - Hunwick, J. O. (Transactions of the Historical Society of Ghana, 1974)
Keywords: Recension

West African Food in the Middle Ages - Wet, J.M.J. de (African Economic History, 1976)
Keywords: Recension

West African Food in the Middle Ages - Garine, Igor de (L'Homme, 1975)
Keywords: Recension

West African Food in the Middle Ages - Siroto, Marie (American Anthropologist, 1976)
Keywords: Recension

Studia nad maghrebem i sudanem - Hadj-Sadok, M. (Arabica, 1977)
Keywords: Recension

West African Food in the Middle Ages - Hirschberg, W. (Anthropologischer Anzeiger, 1976)
Keywords: Recension

West African Food in the Middle Ages, according to Arabic Sources. By Tadeusz Lewicki. London: Cambridge University Press, 1974. Pp. xv, 262, bibl., map. £8.00. - Kirk-Greene, A. H. M. (Africa, 1977)
Keywords: Recension

West African Food in the Middle Ages - Hunwick, J. O. (African Economic History, 1976)
Keywords: Recension

West African Food in the Middle Ages - Perinbam, B. Marie (The Journal of Economic History, 1975)
Keywords: Recension

West African Food in the Middle Ages - Vogt, John (ASA Review of Books, 1976)
Keywords: Recension

L’emploi et les investissements touristiques à Jerba - Mzabi, Hassouna (Revue tunisienne de géographie, 1979)
Keywords: Tourisme -- Djerba

Les tentatives de remodelage de l’espace tunisien depuis l’indépendance - Sethom, Hafedh (Méditerranée, 1979)
Keywords: Urbanisme -- Djerba

Tunisian Cooperatives: Failure of a Bold Experiment - Stone, Russell A. (Africa Report, 1971)

Un épisode de la lutte pour l’indépendance tunisienne l’affrontement de Bourguiba et de Salah Ben Youssef - Julien, Charles-André (Les Temps Modernes, 1976)
Keywords: Ben Youssef, Salah 1907-1961

Une diatribe qui éclaire l'histoire. L'affrontement Bourguiba - Ben Youssef - Bessis, Juliette (Les Temps Modernes, 1976)
Keywords: Ben Youssef, Salah 1907-1961

La déclaration de Jerba - Camau, Michel (Annuaire de l'Afrique du Nord, 1975)

Tourism in South-Tunisia Developments and Perspectives in the Djerba-Zarsis Region - Tempelman, G. J. (Tijdschrift Voor Economische En Sociale Geografie, 1975)
Keywords: Tourisme -- Djerba

Une interview inédite de Salah Ben Youssef - Saumagne, Charles (Les Temps Modernes, 1976)
Keywords: Ben Youssef, Salah 1907-1961

Water and Tribal Settlement in South-East Arabia: A Study of the Aflaj of Oman . J. C. Wilkinson. - Spooner, Brian (American Anthropologist, 1979)
Keywords: Recension

Wilkinson, J. C. 1977: Water and tribal settlement in south-east Arabia. A study of the Aflåj of Oman. Oxford Research Studies in Geography. Oxford University Press. xvi+276 pp. £12.50 - Doornkamp, J.C. (Progress in Physical Geography: Earth and Environment, 1978)
Keywords: Recension

J. C. WILKINSON, Water and tribal settlement in south-east Arabia. A study of the Aflâj of Oman, Oxford research studies in geography, Clarendon Press. Oxford, 1977, XVI + 276 p. + cartes, diagrammes, bibliographie - Chelhod, Joseph (Arabica, 1979)
Keywords: Recension

Ian Skeet: Muscat and Oman: the end of an era. 224 pp., front., 8 plates. London: Faber and Faber, 1974. £3.95. - Wilkinson, John Craven (Bulletin of the School of Oriental and African Studies, 1975)
Keywords: Recension

J. C. Wilkinson: Water and tribal settlement in south-east Arabia: a study of the aflāj of Oman. (Oxford Research Studies in Geography.) xvi, 276 pp. Oxford: Clarendon Press, 1977. £12.50. - Serjeant, Robert Bertram (Bulletin of the School of Oriental and African Studies, 1979)
Keywords: Recension

The Oman Question: The Background to the Political Geography of South-East Arabia - Wilkinson, John Craven (The Geographical Journal, 1971)

Water and Tribal Settlement in South-East Arabia: A Study of the Aflaj of Oman - Cumming, Duncan (The Geographical Journal, 1978)
Keywords: Recension

The Kharijites and the Murjiʼites from Shahrastani's Kitab Al-Milal Waʼl-Niḥal - Kazi, A. K.; Maulvi, Fazil; Flynn, J. G. (Abr-Nahrain, 1970)
Keywords: Kharijisme

Religious Ethic and the Spirit of Capitalism in Tunisia - Stone, Russell A. (International Journal of Middle East Studies, 1974)
The relationship between religion and entrepreneurial activity has been an ongoing subject of sociological interest since Weber (1958) first identified the association between Protestantism and the rise of capitalism in Western Europe. One recent collection of papers on the subject (Eisenstadt, 1968) indicates that the topic remains highly controversial, and that the debate moves in two general directions. Some analysts challenge (or support) the factual and/or theoretical validity of Weber's analysis as it applies to Western Europe, or to Protestantism (Green, 1959). Another branch of research attempts to apply the idea on a different level, finding other religious groups for which the theory is valid, in other parts of the world. Most such studies have been made in East and Southeast Asia, but there is a scattering of articles on other countries as well (Eisenstadt, 1968). Bellah (1963) cites several studies of merchant groups in Asia which conform to the Protestant ethic pattern, but points out that they seldom transform the norms of the whole society as Protestantism did in parts of Europe. Their impact is limited to a subgroup within society. These studies suggest that the Weberian thesis might apply on an intra-societal level in cultures different from Europe. The present study attempts to support this idea by positing a relationship between religious ethic and capitalism among a group of merchants in Tunisia who are members of a distinct religious sect within Islam.
Keywords: Commerce -- Djerba

Pterygium on the Island of Djerba in Southern Tunis - Dolezalová (Klinische Monatsblatter Fur Augenheilkunde, 1974)
Keywords: Biologie -- Djerba

Tribes and Politics in Eastern Arabia - Peterson, John E. (Middle East Journal, 1977)
Keywords: Vie politique -- Oman -- 1970-2020

Nachträge zu meinem Aufsatz Untersuchungen zu einigen ibaditischen Handschriften - Ess, Josef van (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1977)
Keywords: Manuscrits -- Ibadisme

Untersuchungen zu einigen ibaditischen Handschriften - Ess, Josef van (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1976)
Descriptions, with many detailed annotations, of: - Jābir b. Zayd al-Azdī (d. between 93/711 and 104/722): Rasā’il. MSS in al-Khizānat al-Bāruniyya. (Ennami 1971, 65-66 (75?); Nachträge, 1-2). - Qatāda b. Diʿāma (d. 117/735 or 118/736): Aqwāl Qatāda. 7 parts. In Makt. Sālim b. Yaʿqūb. (Ennami 1971, 31 ff.; Nachträge, 2). (Ess 1986). - al-Rabīʿ b. Ḥabīb b. ʿAmr al-Farāhīdī: al-Musnad or al-Jāmiʿ al-Ṣahīḥ. (Nachträge, 2). - Abū Ghānim Bishr b. Ghānim al-Khurāsānī: al-Mudawwana. (Ennami 1971, 155 ff.; Nachträge, 2-3). - Hūd b. Muḥkim al-Hawwārī: Tafsīr. (Nachträge, 3). - Anonymous: Kitāb al-Jahālāt. (Nachträge, 3). - Abū Muḥ.: Kitāb al-Ḍiyā’. MS with Ṣāliḥ Bāʿimāra in Melika. - Anonymous: Dīwān al-Ashyākh. In al-Khizāna al-Bārūniyya, and two parts with Ṣāliḥ Bāʿimāra in Melika. - Abū Zak. Yaḥyà b. Abī Bakr al-Warjlānī (d. 471/1078): Kitāb al-Sīra wa-Akhbār al-A’imma. MS with Ṣāliḥ Bāʿimāra in Melika. (Nachträge, 3). - Tibghūrin (b. Bakr b. Jawād) b. ʿĪsà b. Dāwud al-Nafūsī al-Malshūṭī (d. circa 500/1106): Kitāb al-Uṣūl. With Ṣāliḥ Bāʿimāra in Melika. (Ennami 1971, II; Nachträge, 3). - Abū ʿAmr ʿUthmān b. Khalīfa al-Ṣūfī (1st half 6th/13th c.): Kitāb al-Su’ālāt. Incomplete MS with Ṣāliḥ Bāʿimāra in Melika. - Abū ʿAmmār ʿAbd al-Kāfī b. Abī Yaʿqūb b. Ism. al-Tanāwutī: Kitāb al-Mūjaz fī Taḥṣīl al-Su’āl wa-Takhlīṣ al-Ḍalāl. MS with Matharī (=Mutahhar) Ḥājj Muḥ. in Melika. - Abū ‘l-ʿAbbās Aḥm. b. Saʿīd al-Shammākhī (d. 928/1522): Mukhtaṣar Kitāb al-ʿAdl by Abū Yaʿqūb Yūsuf b. Ibr. al-Warjlānī. MS with Ṣāliḥ Bāʿimāra in Melika. (Ennami 1971, 292 ff.; Nachträge, 3-4). - Aḥm. b. Saʿīd al-Darjīnī (d. 2nd half 7th/13th century): Ṭabaqāt al-Mashāyikh. MS with Ṣāliḥ Bāʿimāra in Melika. - K. al-As’ila wa’l-Ajwiba li-Ahl ʿUmān. - Muḥ. b. Sul. b. Ṣāliḥ al-Mīzābī: Naẓm al-Nīl. (See Maghrib, Yasjanī, Abū ʿAbdl. Muḥ. b. Sul. b. Ṣāliḥ al-Mīzābī). - Muḥ. b. Yūsuf Iṭfayyish: commentary on Maʿālim al-Dīn of ʿAbd al-ʿAzīz al-Thamīnī. Autograph MS with Ṣāliḥ Bāʿimāra in Melika. - Muḥ. b. Yūsuf Iṭfayyish: commentary on the Lāmiyya of Ibn al-Naẓar. MS with Ṣāliḥ Bāʿimāra in Melika. (Nachträge, 4).
Keywords: Bibliographie; Bibliothèques -- Mzab; Manuscrits -- Djerba; Manuscrits -- Mzab

Notes On Some Indo-Pacific Pontoniinae. Xix. Allopontonia Iaini Gen. Nov., Sp. Nov., a New Echinoid Associate From Zanzibar (Decapoda, Caridea) - Bruce, A.J. (Crustaceana, 1972)
Keywords: Zanzibar

Kûfan Political Alignments and their Background in the Mid-Seventh Century a.d. - Hinds, Martin (International Journal of Middle East Studies, 1971)
The period of the so-called Patriarchal Caliphs continues to be rich with questions which can be investigated only with material which often seems less than adequate. Among the more intriguing questions are those connected with the rôle of Kûfa and the emergence there of the political alignments with which representatives both of the early Umayyad caliphs and of the anti-caliph Ibn al-Zubary had later to deal, viz. the Khawârij, the Shi'a and the tribal ashrâf. The remarks in this article are intended to present a broad picture of conclusions reached in a more detailed study of the formation of these political alignments – conclusions which are based on evidence contained in the earliest Islamic historical sources available to us, notably those of al-Balâdhurî, al-Tabarî, Ibn Sa'd, Ibn A'tham al-Kûfî, Khalîfa b. Khayyât and Nasr b. Muzâhim al-Minqarî.
Keywords: Qurra

The Murder of the Caliph 'Uthmân - Hinds, Martin (International Journal of Middle East Studies, 1972)
The murder of ‘Uthmân was an important turning-point in Islamic history, and the story of how opposition in the provinces, particularly Egypt, combined with opposition at Medina itself and brought about the Caliph's death has been repeated many times. Accounts in sources such as al-Tabarî's History and al-Balâdhurîs Ansâb al-ashrâf bring together much transmitted detail concerning this dénouement. Caetani's monumental Annali dell'Islam serves as an extensive compilation of such detail, and Wellhausen, Levi Delia Vida, Gibb, Veccia Vaglieri and Petersen are only some of the other modern scholars who have commented on the event. Perhaps Professor Gibb best expresses the current view of the background to it in his thought-provoking article entitled ‘An interpretation of Islamic history’, where he sees in the caliphate of 'Uthmân a conflict between two main parties, the Meccans and the ‘tribesmen’. He points out that the Meccan merchants had been swift to seize the opportunities of wealth which arose in the immediate post-conquest phase, and goes on to say that in the course of 'Uthman's caliphate there arose at Medina ‘growing resentment at the rapid affirmation of Meccan political control… and the economic exploitation of the empire. Open discontent was first expressed by several religious personalities, whose conscience was shocked by the worldliness and grasping materialism displayed in the name of Islam. But these only provided a rallying-cry and a cloak for the material grievances of the tribesmen and Medinians, who swung into line behind them.’ Gibb therefore sees a total of four alignments, of which the Meccans and the tribesmen were the main parties, while the Medinans and the so-called religious party were secondary in importance.
Keywords: Fitnah

The Banners and Battle Cries of the Arabs at Ṣiffīn - Hinds, Martin (al-Abhath, 1971)
Keywords: Fitnah

Jacques Grand'henry: Les parlers arabes de la région du Mzāb (Sahara algérien). (Studies in Semitic Languages and Linguistics, v.) xx, 136 pp. Leiden: E. J. Brill, 1976. Guilders 48. - Johnstone, Thomas Muir (Bulletin of the School of Oriental and African Studies, 1977)
Keywords: Recension

Urban communities of the Algerian Sahara - Delaval, Bernard (Ekistics, 1974)
Keywords: Urbanisme -- Mzab

Large-scale landslides in north-western Libya - Ostaficzuk, Stanislaw (Acta Geologica Polonica, 1973)
Keywords: Géologie -- Djebel Nefousa

Hotel Darjerba, Djerba, Tunesien - Bremer, Claus (Arkitektur Denmark, 1975)
Keywords: Architecture -- Djerba

À Djerba quand la tradition s'impose au contemporain - Gautier-Delaye, Pierre (Plaisir de France, 1975)
1. Une architecture séculaire née de la Méditerannée 2. Le Djerba-Menzel, une unité hôtelière issue des formes ancestrales
Keywords: Architecture -- Djerba

Hôtel à Djerba - Gautier-Delaye, Pierre (Recherche et architecture : supplément à cahiers du Centre scientifique et technique du bâtiment, 1975)
Keywords: Architecture -- Djerba

Mohammed ben Juma el-Murjebi, père de Tippo Tip - Bontinck, François (Bulletin des séances / Académie Royal des Sciences d'Outre-Mer, 1979)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo Tip, traitant et organisateur d'Etat - Kinenge, Kimena Kekwaka (Zaïre-Afrique : économie, culture, vie sociale Zaïre-Afrique, 1979)
Keywords: Tippo Tip (1837-1905); Zanzibar

La double traversée de l'Afrique par trois "Arabes" de Zanzibar, 1845-1860 - Bontinck, François (Etudes d'Histoire Africaine, 1974)
Keywords: Esclavage -- Zanzibar

Restauration d’ateliers de tisserands à Djerba (Tunisie) - Calpini, Gustavo; Calpini, D. (L’Architecture, 1976)
Keywords: Architecture -- Djerba

L’architecture de Jerba - Canavate, Christian; Roussel, Pierre (Echanges, 1979)
Keywords: Architecture -- Djerba

Die Mozabiten. Ein anthropologischer Ausflug ins Tal des Mzab - Freund, Wolfgang Slim (Zeitschrift für Kulturaustausch, 1970)
Keywords: Moeurs et coutumes -- Mzab

Social control amongst the Mzabite women of Beni‐Isguen - Farrag, Amina (Middle Eastern Studies, 1971)
Keywords: Moeurs et coutumes -- Mzab

Les parlers arabes de la region du Mzab (Sahara algerien) - Singer, Hans-Rudolf (Die Welt des Islams, 1979)
Keywords: Recension

Journal de Djerba-la-Douce - Lobet, Marcel (Revue générale, 1974)
Keywords: Tourisme -- Djerba

Il y a dix ans déjà... A mon collègue et ami Charles Kleinknecht - Moriaz, Jean (Le Saharien, 1978)
Keywords: Moeurs et coutumes -- Mzab

Le Bordj - Moriaz, Jean (Le Saharien, 1971)
Keywords: Moeurs et coutumes -- Mzab

L'Iliade algérienne - Zakaria, Moufdi (El Assala, 1972)

Report from Algeria's Mzab - Wolff, Ursula (Africa Report, 1976)
Keywords: Récits de voyage -- Mzab

Formation de la conscience sociale supratribale en partant des conditions ethniques du Sahara occidental - Komorowski, Zygmunt (Africana Bulletin, 1975)

Paysage: l’île de Djerba - Ghitelman, Davis (Agni, 1974)
Keywords: Littérature -- Djerba

A proposito della terminologia marinaresca zuarina (Immagini comuni ad altre zone del Mediterraneo e prestiti italiani) - Serra, Luigi (Bollettino dell’Atlante Linguistico Mediterraneo, 1970)
Keywords: Linguistique -- Zouara

I ‘nomina actionis’ in un dialetto berbero orientale (Zuara-Tripolitania) - Serra, Luigi (Aiōn: Annali del Seminario di Studi del Mondo Classico, Sezione Linguistica, 1979)
Keywords: Linguistique -- Zouara

Concordanze dialetti italiane con voci arabe e berbere e voci italiane in un dialetto berbero tripolitano - Serra, Luigi (Bollettino dell’Atlante Linguistico Mediterraneo, 1976)
Keywords: Linguistique -- Djebel Nefousa

L’ittionimia e la terminologia marinaresca nel dialetto berbero di Zuara (Tripolitania) - Serra, Luigi (Studi Magrebini, 1970)
Keywords: Linguistique -- Zouara

Gli uomini piu venerati dai Berberi Ibaditi di Zuara (Tripolitania) - Serra, Luigi (Studi Magrebini, 1971)
Keywords: Linguistique -- Zouara

Berberische Nomina Actoris im Dialekt des Djebel Nefusa (Tripolitanien) - Vycichl, Werner (Orientalistische Literaturzeitung, 1972)
Keywords: Linguistique -- Djerba

Testi berberi di Žâdu - Provasi, Elio (Istituto Orientale di Napoli, 1973)
Keywords: Linguistique -- Djebel Nefousa

Intervista nel Nefûsa. Marabutti della zona di Zâdû - Chiauzzi, Gioia (Oriente Moderno, 1971)
Lors d’une mission dans le Jebel Nefoussa, Gioia Chiauzzi a pu enregistrer une interview qu’elle a conduite à Jadu auprès d’un agriculteur. Elle enquêtait alors sur les rites agricoles et notamment sur l’importance du rôle de l’intervention des marabouts locaux. Elle a ainsi obtenu un texte qui porte essentiellement sur une source d’eau sacrée de la région : la source de Nânnā Tâlā, une femme marabout, et sur les rites qui y sont liés. Ce texte présente un intérêt ethnologique car il traite notamment de l’ordalie et de la foi dans les propriétés de cette source.
Keywords: Croyances populaires -- Djebel Nefousa

Some mosques of the Jebel Nefusa - Allan, J. W. (Libya Antiqua, 1972)
Keywords: Architecture -- Djebel Nefousa

L’isola di Djerba - Traversi, Carlo (Universo, 1972)
Keywords: Récits de voyage -- Djerba

Hôtel Djerba-Menzel - Gautier-Delaye, Pierre (L’Architecture Française, 1972)
Keywords: Architecture -- Djerba

Jerba, structure urbaine - Jelassi, F. (Art, Architecture, Aménagement, 1978)
Keywords: Architecture -- Djerba

Libre propos: Djerba - Joly, Pierre (Recherche et architecture : supplément à cahiers du Centre scientifique et technique du bâtiment, 1977)
Keywords: Architecture -- Djerba

Notules de Préhistoire mozabite - Morel, J. (Libyca, 1976)
Keywords: Archéologie -- Mzab

Jean-Marie Dallet - Lanfry, Jacques (Libyca, 1972)
Keywords: Biographies -- France

Notes de préhistoire tiarétienne II - Objets de parure et amulettes - Cadenat, Paul (Libyca, 1971)
Keywords: Archéologie -- Mzab

Aperçu sur l'évolution du paysage quaternaire et le peuplement de la région de Ouargla - Aumassip, Ginette (Libyca, 1972)
Keywords: Peuplement -- Ouargla

État actuel du nomadisme dans la région de Ouargla (Sahara algérien) - Romey, Alain (Libyca, 1977)
Keywords: Moeurs et coutumes -- Ouargla; Nomadisme -- Ouargla; Ouargla -- Histoire

Contribution à l'étude de l'habitat au M'zab - Bonète, Yves (Cahier des Arts et Techniques d'Afrique du Nord, 1974)
Keywords: Urbanisme -- Mzab

La Pentapole du M'zab: persuader pour conserver - Roche, Manuelle (Architecture d'Aujourd'hui, 1976)
Keywords: Architecture -- Mzab; Monuments -- conservation -- Mzab

Nostalgie De La Fête Chez Les Juifs Du M'Zab (sud-algérien) Réfugiés En Alsace - Raphaël, Freddy (Revue des Sciences Sociales de la France de l'Est, 1979)
Keywords: Judaïsme -- Mzab

The linguistic situation in independent Tunisia - Maamouri, Mohamed (American Journal of Arabic Studies, 1973)
Keywords: Linguistique

Étude du dialecte berbere de Guellala (île de Djerba) - Vycichl, Werner (Bulletin d’Information et de Liaison, CARDAN, 1973)
étude d’un parler en voie de disparition : phonétique, grammaire, textes, ethnographie
Keywords: Linguistique

I dialleti berberi orientali (Rassegna degli studi e prospettiva di ricerca) - Serra, Luigi (Atti del Sodalizio Glottologico Milanese, 1979)
Keywords: Linguistique

Les plans d'aménagements touristiques - Barbouch, Abdellatif (Art, Architecture, Aménagement, 1978)
Keywords: Architecture -- Djerba

Association de sauvegarde de l'ile (Art, Architecture, Aménagement, 1978)
Keywords: Architecture -- Djerba

Séminaire sur la sauvegarde de Jerba (Art, Architecture, Aménagement, 1978)
Keywords: Architecture -- Djerba

Les matériaux et les techniques de construction - Hantous, Tahar; El Younsi, Salah (Art, Architecture, Aménagement, 1978)
Keywords: Architecture -- Djerba

Robert Lachmann: his Achievement and his Legacy - Gerson-Kiwi, Edith (Yuval, 1974)
Keywords: Judaïsme -- Djerba

Ritualization of literacy: the works of Tunisian scholars in Israel - Deshen, Shlomo (American Ethnologist, 1975)
Book publishing is an act of piety among the Tunisian immigrants of Israel. The literary content of books is less important than their talismanic value. The Tunisian community in Israel has abandoned many of its traditional religious practices, substituting for them pious acts such as pilgrimages and the publishing of religious books.
Keywords: Judaïsme -- Djerba

Ethnicity and Citizenship in the Ritual of an Israeli Synagogue - Deshen, Shlomo (Southwestern Journal of Anthropology, 1972)
Tension between citizenship and ethnicity is expressed in an Israeli ethnic synagogue by changes in ritual and symbolism. The symbolic expression of these changes relates worshippers of the synagogue, who are recent immigrants to Israel, to their new heterogenous environment. Analysis of the changes in symbols demonstrates that the referential aspects have expanded, consistent with alterations in traditional relationships. The reinterpreted symbols may be categorized in terms of a typology of religious change as instances of "innovation," in the sense that the experiential range to which the symbol applies has been changed.
Keywords: Judaïsme -- Djerba

An Outline of the Social Structure of the Jewish Communities in Djerba and Southern Tunisia from the End of the 19th Century until the 1950's / קווים למבנה החברתי של קהילות יהודי ג'רבה ודרום טוניסיה מסוף המאה היט עד לעליות ארצה - דשן, שלמה; Deshen, Shlomo (Zion / ציון, 1976)
Southern Tunisian Jewry has an uninterrupted and relatively peaceful history going back into antiquity. The general Berber population, particularly of the island of Djerba, has since the late 19th century developed a pattern of migrant merchants, who operate throughout Tunisia and retire in their old age to their homes. In this context, the Jews entered local commerce and filled the major local positions, however they did not engage in international or in itinerant commerce or trade. Djerban Jewry is therefore extremely sedentary and lacking in geographic mobility. As a consequence, the local community is relatively powerful over its individual members. Social control, particularly in religious matters, is strong because of the high visibility of individuals. Community organs are highly developed in comparison to other Jewish communities in North Africa. The continued development of community organs in the period under discussion is described in the paper on the basis of rabbinical treatises of recent generations.
Keywords: Judaïsme -- Djerba

Towards a Description of the Traditional Pronunciation of the Jewish Community of Djerba / לתיאורה של מסורת ההגייה העברית של קהילת ג'רבה (תוניסיה) - Katz, Ktzia (Proceedings of the World Congress of Jewish Studies / דברי הקונגרס העולמי למדעי היהדות, 1973)
Keywords: Judaïsme -- Djerba

The Varieties of Abandonment of Religious Symbols: Changes in Ethnic Synagogue / גוונים של נטישת סמלים דתיים: שינויים בבית כנסת עדתי - Deshen, Shlomo (Megamot, 1971)
Taking the Weberian use of the term "secularization" as a point of departure, the author questions a recent identification of the term with the abandonment of religious beliefs per se. He shows that an abandoning of religious beliefs, which can be effected either through the eradication or the effacement (terms he posits in his typology of religious changes) of religious symbols, is not necessarily an index of secularization. The two concepts in turn are demonstrated to be distinct phenomena growing out of very different sociological conditions and circumstances. Three cases of symbolic change which occurred in a Djerban synagogue in Israel are discussed and the analysis is extended through a comparison with an African ritual. The three Djerban examples in the Israeli environment and the African ritual were found to be instances of effacement. In all four cases the very act of abandonment of the religious symbols, which was due to the fact that the particular symbols in question no longer conforms with the experiential situation of the actors, led to a reaffirmation of the symbols.
Keywords: Judaïsme -- Djerba

The Writing of Tunisian Sages in Israel / כתבי חכמי טוניסיה בישראל - Deshen, Shlomo; בוכריס, דוד; פרג'ון, פורטונה (Megamot, 1975)
This article deals with one aspect of the cultural and social problems encountered by Tunisian Jews in the course of their absorption in Israel. The article concentrates on the study of one of the outstanding occupations distinguishing the community — the publication of the works of Jewish sages, especially from Djerba Island. The publication of religious books, most of which are commentaries on the Bible and the Talmud, was a common phenomenon among the Jews of Djerba Island in particular. If the author of the work was dead, the publication of the work by the descendants raised the latter's social status since it proved that learning and wisdom were part of their family legacy. It also contained an element of honour for one's parents. After immigration to Israel another motive was added to the wish to publish the religious commentaries of a father or other relative — the desire to rescue these writings from oblivion in view of the decline of religious tradition and the secularization process among members of the Tunisian community The activity involved in publication among South Tunisian Jews is thus studied against the background of a rich religious-cultural tradition in which importance was attached to writing and publication and a present which is conceived as an age of decline and degeneration as far as religion is concerned. The amount of books published and circulated is relatively large considering the potential reader market — Jews who immigrated to Israel from South Tunisia. The findings reveal that the relatively wide circulation is not to be attributed to an improvement in their economic situation or the desire of people for prestige and social recognition. These factors explain only part of the phenomenon. A fuller explanation may be presented in symbolic and cultural terms. By engaging in publication or financing it, people express their respect for the deceased, especially if the authors are their ancestors. From this point of view, the content of the book is unimportant because the books as such has a religious value of its own and it is intended to express the loyalty of children to their fathers. This phenomenon may also be defined as the ritualization of literature. Another aspect of this ritualization is that a magical protective power is attached to the book i.e. the latter serve as amulets. This ritualization is apparently a substitute for the numerous specific religious acts many of which are no longer performed today. Instead of them, various activities to which a defusive religious value is attached, are now making their appearance.
Keywords: Judaïsme -- Djerba

Ethnicity and Citizenship in the Ritual of a Synagogue of Tunisian Immigrants / עדתיות ואזרחות בבית-הכנסת של עולי טוניסיה בישראל - Deshen, Shlomo (Megamot, 1971)
The paper examines the nature of the changes in ritual that occurred in an Israeli ethnic synagogue and their symbolic expressions, particularly the tension between citizenship and ethnicity. Certain events taking place in, or concerning, a particular synagogue were studied. The symbolic expression of the changes was found to be a means of communion of the worshipper with his new heterogeneous environment. The symbolic reference was now wider and the symbolic changes implied a shift in a relationship formerly obtained. In order to analyse the symbolic changes more definitely, the author developed a typology of religious changes comprising several types of symbolic changes of which the examples in this paper fall into the category of "innovation."
Keywords: Judaïsme -- Djerba

Les musulmans et les Israélites tunisiens dans l’agglomération parisienne 1970 - Simon, Gildas (Population, 1974)
Keywords: Démographie -- Djerba

L’émigration tunisienne en particulier pour le Sud Tunisien - Picouet, Michel (Population, 1974)
Keywords: Démographie -- Djerba

Aperçu des migrations intérieures en Tunisie - Picouet, Michel (Population, 1971)
Keywords: Démographie -- Djerba

L’émigration dans le Sud Tunisien - Mzabi, Hassouna (Revue tunisienne de géographie, 1979)
Keywords: Démographie -- Djerba

Contribution à l’étude hydrologique du bassin de Bou-Grara (Sud-Est Tunisien) - Jedoui, Younes (Notes du service géologique, 1979)
Keywords: Géologie -- Djerba

Djerba: Avant et après - Sigisbert, Geneviève (Europe Outremer, 1974)
Keywords: Géographie -- Djerba

L’érosion des plages dans le sud tunisien : exemples à Jerba (côtes Est et Sud-Est) et à Zarzis - Miossec, Jean-Marie; Paskoff, Roland (Revue tunisienne de géographie, 1979)
Keywords: Littoraux -- Djerba

Les formations quaternaires de l’île de Jerba (Tunisie) ; essai sur les lignes de rivage - Paskoff, Roland; Sanlaville, Paul (Bulletin de la Societe Geologique de France, 1977)
Keywords: Géologie -- Djerba

Sur l’origine de la formation Tlet et sa place dans la stratigraphie du Quaternaire recent de la region de Djerba - Zarzis (Sud tunisien) - Paskoff, Roland; Sanlaville, Paul (Comptes Rendus Hebdomadaires des Séances de l’Académie des Sciences, 1978)
Keywords: Géologie -- Djerba

L’érosion des plages dans la sud Tunisien - Paskoff, Roland (Revue tunisienne de géographie, 1979)
Keywords: Géologie -- Djerba

Un espace côtier à protéger : la flèche littorale de Ras Rmel à Jerba - Paskoff, Roland (Echanges, 1979)
Keywords: Géologie -- Djerba

Le Lambeau de Tlet et la structure néotectonique de l’ile de Jerba (Tunisie) - Perthuisot, Jean-Louis (Comptes Rendus Hebdomadaires des Séances de l’Académie des Sciences, 1977)
Keywords: Géologie -- Djerba

Le quaternaire récent de Jerba et de la presqu’île de Zarzis - Paskoff, Roland; Sanlaville, Paul (Revue tunisienne de géographie, 1979)
Keywords: Géologie -- Djerba

L'architecture populaire à Jerba - Joly, Pierre (Revue tunisienne de l'équipement, 1977)
Keywords: Architecture -- Djerba

Le « lambeau de Tlet » et la structure néotectonique de l’île de Jerba (Tunisie) - Glangeaud, Louis; Perthuisot, Jean-Louis (Comptes Rendus Hebdomadaires des Séances de l’Académie des Sciences, 1977)
Keywords: Géologie -- Djerba

Rivage holocène supérieur à l’actuel en Tunisie méridionale, Les indicateurs de niveaux marins - Dalongeville, Rémi; Paskoff, Roland (Oceanis, 1979)
Keywords: Géologie -- Djerba

Morphologie littorale des roches carbonatéses à Jerba (Tunisie) - Dalongeville, Rémi (Revue tunisienne de géographie, 1979)
Keywords: Géologie -- Djerba

Hassouna Mzabi, La croissance urbaine accélérée à Jerba et ses conséquences sur la vie de relation avec l'extérieur - Miossec, Jean-Marie (Méditerranée, 1973)
Keywords: Recension

Croissance et environnement à Jerba (Tunisie) - Miossec, Jean-Marie (Bulletin de l'Association de géographes français, 1976)
Keywords: Démographie -- Djerba

Evolution des plages et aménagements touristiques à Jerba (Tunisie): Le cas du littoral nord-est de l'île - Miossec, Jean-Marie; Paskoff, Roland (Méditerranée, 1979)
Keywords: Tourisme -- Djerba

Quelques groupements végétaux nitrophiles reconnus à Djerba (Tunisie méridionale) - Vanden Berghen, Constant (Documents Phytosociologiques, 1979)
Keywords: Botanique -- Djerba

Premier examen du plancton végétal et animal des parages de l’ile de Djerba - Bernard, Michelle; Bernard, Francis (Rapports et Proces-verbaux des Réunions. Commission Internationale pour l’Exploration Scientifique de la Mer Méditerranée, 1973)
Keywords: Faune -- Djerba

Observations sur la végétation de l’île de Djerba (Tunisie méridionale): note 3: les dépressions dans les dunes littorales - Vanden Berghen, Constant (Bulletin de la Société Royale de Botanique de Belgique / Bulletin van de Koninklijke Belgische Botanische Vereniging, 1979)
Six plant-associations are noticed in the dune slacks of Djerba: an aquatic one with Ruppia cirrhosa, a community on wet sands with Riella notarisii, an association with Limonium tunetanum and Aeluropus lagopoides, an association with Juncus maritimus var. arabicus, an association with Schoenus nigricans, a pioneer community with Frankenia pulverulenta. Description of the communities; ecological data; phytogeographical considerations. Sechs Pflanzengemeinschaften werden erkannt und beschrieben: eine monophytische Wassergemeinschaft von Ruppia cirrhosa, eine ephemere Gemeinschaft von Lebermoos Riella notarisii, eine Assoziation von Limonium tunetanum und Aeluropus lagopoides, eine Assoziation von Juncus maritimus var. arabicus, ein Assoziation von Schoenus nigricans und eine Pionniergesellschaft von Frankenia pulverulenta. Ökologische und pflanzengeographische Bemerkungen.
Keywords: Botanique -- Djerba

Observations sur la végétation de l’île de Djerba (Tunisie méridionale): note 2 : les dunes fixées. l’association à imperata cylindrica et ononis angustissima - Vanden Berghen, Constant (Bulletin de la Société Royale de Botanique de Belgique / Bulletin van de Koninklijke Belgische Botanische Vereniging, 1978)
Description of the plant community noticed on the dry fixed coastal sands. Ecological data. Phytogeographical considerations; importance of the saharo-sindian element. Beschreibung des öffene Pflanzenkleid der ruhende Dünen. Oekologische und pflanzengeographische Bemerkungen; Rolle des saharo-sindische Element.
Keywords: Botanique -- Djerba

Observations sur la végétation de l’île de Djerba (Tunisie méridionale): note 1: introduction et végétation des dunes mobiles - Vanden Berghen, Constant (Bulletin de la Société Royale de Botanique de Belgique / Bulletin van de Koninklijke Belgische Botanische Vereniging, 1977)
Observations on the vegetation of the island of Djerba (South Tunisia). 1: Introduction. Vegetation of the coastal sands. — Two plant-associations are noticed in the dunes of Djerba: an oriental variant of Agropyretum mediterraneum, on the low dunes of the upper beach, and Ammophiletum arundinaceae, on the high dunes. Ecological data. Phytogeographical considerations. Zwei Pflanzengemeinschaften spielen eine Rolle in der Erbauung der Dünen: eine österliche Variante von Agropyretum mediterraneum auf dem Hochstrand, und Ammophiletum arundinaceae auf die höchsten Dünen. Oekologische und pflanzengeographische Bemerkungen.
Keywords: Botanique -- Djerba

La description des côtes de la Tunisie dans le Kitâb-i Bahriye de Piri Reis - Mantran, Robert (Revue de l'Occident musulman et de la Méditerranée, 1977)
Keywords: Cartes -- Djerba

Le tourisme à Djerba, répercussions sociales - Freund, Wolfgang Slim (Revue de l'Occident musulman et de la Méditerranée, 1970)
Keywords: Tourisme -- Djerba

Le travail de la laine à Ghardaïa - Allain, Madeleine; Delheure, Jean (Revue de l'Occident musulman et de la Méditerranée, 1979)
Keywords: Artisanat -- Mzab

Croissance urbaine au Sahara : Ghardaïa - Josse, Raymond (Cahiers d'Outre-Mer, 1970)
Keywords: Urbanisme -- Mzab

A description of new Ibadi Manuscripts from North Africa - Nāmī, ʿAmr Khalīfa al- (Journal of Semitic Studies, 1970)
Keywords: Bibliothèques -- Djebel Nefousa; Bibliothèques -- Djerba; Manuscrits -- Djebel Nefousa; Manuscrits -- Djerba

Fragments de mosaïques de Djerba, conservés au musée de Blois - Blanchard-Lemée, Michèle (Antiquités africaines, 1978)
Keywords: Antiquité; Archéologie -- Djerba

Pantelleria entre l'Islam et la Chrétienté - Bresc, Henri (Cahiers de Tunisie, 1971)
Keywords: Relations -- Djerba -- Pantelleria

L'habitat traditionnel de Jerba: un probleme d'avenir: essai de reamenagement de certains menzels pour leur integration dans la vie contemporaine - Akkari-Weriemmi, Jenina (Revue de l'Institut des Belles Lettres Arabes, 1977)
Keywords: Architecture -- Djerba